Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 1403034696 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "OccurrenceStatus is Present", "Year 2001-2021" ] } The dataset includes 1403034696 records from 20804 constituent datasets: 3518 records from MCP-Aves - Coleção de Aves. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 100 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 143 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 43 records from Bird specimens of Saitama Museum of Natural History. 29 records from orthopteracollections-nhmj-ioj. 57 records from Invasive alien species Impatiens glandulifera Royle in the Republic of Karelia. 1 records from Review of the millipede tribe Polydrepanini, with the description of a new species from Kerala state, southern India (Diplopoda, Polydesmida, Paradoxosomatidae, Alogolykinae). 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 10752 records from Collections of Bioclass, school #179, Moscow. 6 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 336 records from Aves del cerro Tapartó, Santa Cecilia - Risaralda. 2020. 314 records from Mycology collection, Norwegian Forest and Landscape Institute. 11 records from New Records of ground beetles for Colombia (Coleoptera: Carabidae). 54550 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2016. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 988 records from flower availability 2008 Alb-korrigiert. 14576 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 42 records from Inventaire des Octocoralliaires des fonds sédimentaires de la région niçoise. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 8 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 28076 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 33 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 2804 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 46 records from Brachymelecta Linsley, 1939, previously the rarest North American bee genus, was described from an aberrant specimen and is the senior synonym for Xeromelecta Linsley, 1939. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 29 records from UWIZM Anoles. 2 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 162 records from Condamine Alliance. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 242 records from Herbarium of the Institute of the problems of Northern development (TMN). 7 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 324 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 167 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 748 records from AMAPPS Northeast Aerial Cruise Summer 2010. 62 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 12554 records from Microbial community in marine sediments. 18 records from Naturtag. 45 records from données espèces - Expertise IPE 63. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 8 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 83 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 3018 records from Herbier Louis-Marie (QFA) - Collection de lichens. 41 records from HRC CRC Small Vessel-Based Monitoring Surveys July 2006. 1 records from A new Rhopalomeris species (Diplopoda: Glomerida: Glomeridae), and notes on the phylogenetic relationships between glomeridans in Vietnam. 18 records from Chaoborus flavicans Meigen (Diptera, Chaoboridae) is a complex of lake and pond dwelling species: a revision. 3 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 9 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 2 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 2 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 34 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 1087 records from MZFC/Coleccion de Aves. 1190 records from Coleópteros presentes en un proceso de restauración pasiva en bosque seco tropical. 155 records from Manx Wildlife Trust - Records. 24 records from Dubai Turtle Rehabilitation Project (aggregated per 1-degree cell). 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 46 records from DMNS Egg Collection (Arctos). 1 records from A new species of Anteon from Zimbabwe (Hymenoptera, Dryinidae). 1 records from Happywhale - Layard's beaked whale in Southern Ocean. 134 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 214 records from Lepidopterous specimens of Yamagata Prefectural Museum. 251 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 1350 records from Happywhale - Humpback Whale in Arctic Ocean. 93 records from UNCW Hatteras Aerial Survey - Right side - 2015. 71 records from Chronicle of Nature - Phenology of Mushrooms of Pechoro-Ilych State Nature Reserve. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 192 records from The diversity of the genus Aricidea (Polychaeta: Paraonidae) from the Sea of Marmara, with descriptions of two new species and two new records for the Mediterranean fauna. 9174 records from Relevés of Main Vegetation Types of the Prioksko-Terrasnyi Biosphere Reserve (2019-2020). 8 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 26 records from HRC USWEX Aerial-Based Monitoring Surveys 2007. 83803 records from Florida Keys Reef Visual Census 2014. 8 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 59 records from Visual and genetic surveys for odontocete cetaceans in American Samoa 2003-06. 118 records from An updated checklist of aquatic plants of Myanmar and Thailand. 28 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 1 records from Registro de Chromolaena tacotana asociado al proyecto: Relación estructura-actividad anti-cáncer de flavonoides sobre líneas celulares cancerosas. 11198 records from Overvåking av åpen grunnlendt kalkmark i Oslofjordområdet. 376 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 21583 records from Herbarium Universitatis Daugavpiliensis. 1011 records from SCANS II cetacean sightings on primary platform of vessel surveys 2005. 702 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 2208 records from marine sediment metagenome Raw sequence reads. 1 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 1 records from Megaluropidae *. 971 records from Vascular Plants from Praia da Vitória (Terceira, Azores, Portugal). 11991 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 1862 records from Plecoptera. 1 records from Redescription of Luetkenia elongata (Copepoda: Siphonostomatoida: Pandaridae), an Ectoparasite of Luvarus imperialis (Actinopterygii: Perciformes: Luvaridae), with a New Record from Japanese Waters. 5 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 6 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 87 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 7 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 110 records from Bees in the UVM Zadock Thompson Zoological Collection. 12 records from NZCS Brownsberg Nature Park Monitoring. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 371 records from IOV-UDO-ZOOPLANCTON-PLAYA COLORADA. 50026 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 35 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 15 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 6 records from Huangilene, a new genus for the Miltochrista alikangiae (Strand, 1917) species-group, with descriptions of three new species from Indochina, continental China and Taiwan (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 120 records from BIRDRACE The early birds. 1771 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 586 records from RECORD Orthoptera Data. 50076 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 20 records from A new genus and five new species of Neocoelidiinae leafhoppers from Brazil (Insecta: Hemiptera: Cicadellidae) with a key to males. 3814 records from NE Scotland fish records 1800-2010. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 1205 records from Happywhale - Humpback Whale in Indian Ocean. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 6 records from Sächsische Schweiz (Pfaffenstein). 576 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 44 records from Happywhale - Short-beaked Common Dolphin in North Pacific Ocean. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 4 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 4335 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 1 records from Living Cirripedia. 7 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 3190 records from Organism occurrence records identified from underwater still imagery collected around Lord Howe Island and Balls Pyramid, southwest Pacific Ocean. 112 records from UNCW Norfolk Canyon Aerial Survey - Right side - 2015. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 1087 records from Tree species composition of natural forest islands in a savanna matrix in the northern Brazilian Amazonia. 359 records from HogWatch Scotland Project - West European hedgehog records between 2019 and 2021. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 84 records from Roter Berg Werdau (Leubnitz). 5 records from Taxonomic notes on the genus Sinodrepanus Simonis, 1985, with description of the male of S. falsus (Sharp, 1875) (Coleoptera: Scarabaeidae: Oniticellini). 218 records from Land and freshwater molluscs of Northern Spain. 3734 records from Données naturalistes de Charlotte PICARD. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 13 records from Five new species of Englerophytum K. Krause (Sapotaceae) from central Africa. 628 records from University of Nebraska State Museum Birds Collection. 19469 records from University of California Santa Barbara Invertebrate Zoology Collection. 6447 records from Fish occurrence in Kama River basin. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 76 records from Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 1 records from Discovery of the male of Colletes yanruae from Yunnan, China (Hymenoptera: Apoidea: Colletidae). 2 records from Vietnamella chebalingensis, a new species of the family Vietnamellidae (Ephemeroptera) from China based on morphological and molecular data. 57 records from CSIRO Yellow Box Fragmentation Project. 5163 records from Entomology Collection at the Natural History Museum of Utah. 3862 records from 台灣花蓮沿海賞鯨活動鯨豚觀測紀錄 (The observation records from the activities of whale and dolphin watching in the offshore of Hualien, Eastern Taiwan). 1221 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 40 records from makran-chabahar-arthropods. 2 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 54805 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 3685 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 81636 records from Fish specimens of Kagoshima University Museum. 18 records from UTEP Invertebrates (Arctos). 288 records from Sea Turtles of Dominica (aggregated per 1-degree cell). 16 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 1285 records from Suivi des aires marines protégées de Moorea - Invertébrés benthiques. 10 records from A taxonomic review of the genus Amicta Heylaerts, 1881 in North Africa, Near and Middle East (Lepidoptera, Psychidae, Oiketicinae, Acanthopsychini). 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 1 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 1 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 27867 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 736 records from MEXU/Leguminosae. 84 records from MIRC NAVFAC Incidental Sightings - Aerial 1965-2014. 6 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 15 records from Inventaire des mammifères du Parc de la Haute-Île (93). 235 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 21 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 1127 records from marine sediment metagenome Metagenome. 3752 records from Microbial ecology of archaeal community in sediment from adjacent waters of Rushan Bay. 71 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 1545 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 371 records from Bannwald Burghauser Forst. 11 records from New England Aquarium Harbor Porpoise Tracking (aggregated per 1-degree cell). 20111 records from SEWBReC Bees, Wasps and Ants (South East Wales). 290 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 5568 records from Fitoplancton de la provincia oceánica del mar Caribe colombiano. Diez años de historia. 366 records from UCSC Elephant Seals (aggregated per 1-degree cell). 1 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 6 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 8 records from HRC Koa Kai Marine Species Monitoring Vessel Surveys November 2010. 10 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 1 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 978 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 154 records from Sorensen distance for herbivores. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 34 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 3597 records from University of Guam Insect Collection. 2 records from Dermaptera of Iran with description of Euborellia angustata sp. nov.. 151 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 2 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 605 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 514 records from Museu de Ciències Naturals de Barcelona: BGJBB. 1 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 158 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 5 records from Hydromedusae observed during night dives in the Gulf Stream. 167 records from AMAPPS Southeast Aerial Cruise Fall 2016. 10603 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche (Plantas). 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 536 records from UWIZM Molluscs. 141 records from Inventaire biodiversité du site Pierre Fabre d'Aignan. 39 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 1226 records from Fish occurrence in Kuban River basin. 59 records from Schulteich Freie Waldorfschule Darmstadt. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 684 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 8 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 327 records from Fototrampeo al interior de las áreas del Banco de Hábitat del Meta de Terrasos. 258354 records from MGYS00005313. 6 records from New species of Phaloria (Orthoptera: Phalangopsidae: Phaloriinae) from West Papua (Indonesia). 181 records from UNCW Norfolk Canyon Aerial Survey - Left side - 2016. 2493 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 876 records from Ensemble des données Odonates. 246 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 7 records from Taxonomic revision of Ceropegia sect. Huernia (Asclepiadoideae, Apocynaceae) in Saudi Arabia with three new combinations. 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 3 records from Happywhale - Green Sea Turtle in North Pacific Ocean. 2065 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 1422 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 12 records from Art´n Vielfalt im Kinderwald. 45 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 50 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 13 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 491 records from Invasive Non-Native Species, Outer Hebrides. 30563 records from Phase 2 Lowland Grassland Survey of Wales. 225 records from AFTT JAX Aerial Survey -Left side- 2014. 191 records from Naturalis Biodiversity Center (NL) - Crustacea. 5 records from Campodeidae (Hexapoda: Diplura) from Kyrgyzstan, Central Asia, with the description of a remarkable new genus and species. 4 records from Cast netting new species: Integrative taxonomy of Distichodus notospilus (Characiformes: Distichodontidae) discovers new species and overlooked areas of endemism in Central Africa. 3 records from A new species, a new combination, and a new record of Crossotarsus Chapuis, 1865 (Coleoptera, Curculionidae, Platypodinae) from China. 432 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 874789 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 237168 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 11 records from Hawksbill turtles in Torres Strait (aggregated per 1-degree cell). 209963 records from DATAVES. 23 records from Herpetofauna asociada a la cuenca del río Quito - Chocó, 2014. 296 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 3752 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1590 records from The Broward College Insect Collection. 1 records from Discovery of Lymantini weevils (Coleoptera: Curculionidae: Molytinae) outside the Americas: Devernodes, a new genus for five new species from Southeast Asia. 14 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 1 records from Glyptotermes chiraharitae n. sp., a new dampwood termite species (Isoptera: Kalotermitidae) from India. 1191 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 41 records from NEON Biorepository Zooplankton Collection (DNA Extracts). 9653 records from Ecosphère_2017_12_18. 642 records from Flora vascular y no vascular:expedición El Consuelo - Proyecto Boyacá BIO UPTC. 8 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 34123 records from Fermanagh Flora. 1387 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 2 records from Transfer of two South American ant species from Tapinoma Foerster 1850 to Forelius Emery 1888 (Hymenoptera: Formicidae: Dolichoderinae). 626 records from Isle of Wight non-native invasive species. 2 records from First record of the genus Microtityus Kjellesvig-Waering, 1966, from Puerto Rico, with description of two new species (Scorpiones: Buthidae). 581 records from Floristic records in the Moscow and Novgorod regions. 4 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 2 records from Description of Bagarius vegrandis, a new species of sisorid catfish from Indochina (Actinopterygii: Siluriformes), with notes on the identity of Bagarius bagarius. 771 records from Weber State University Herbarium. 3 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 78 records from Données de la naturaliste Anna Even. 11 records from Happywhale - Peale's Dolphin in South Atlantic Ocean. 100 records from Molecular phylogeny of the genus Lasiopogon (Diptera: Asilidae) and a taxonomic revision of the bivittatus section. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 3 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 1 records from A new species of crown-antlered deer Stephanocemas (Artiodactyla, Cervidae) from the middle Miocene of Qaidam Basin, northern Tibetan Plateau, China, and a preliminary evaluation of its phylogeny. 81 records from Kystfuruskoger i Tysnes og Fusa. 14 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 915 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 8 records from Die Bachspezies 2008/2009. 148143 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 10 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 248 records from Atlas des Hyménoptères Pompilidae du Massif armoricain et des départements voisins : prospections 2018. 7 records from Happywhale - Leatherback Sea Turtle in North Pacific Ocean. 1902 records from Midden-Limburg Fish Ponds Survey. 4 records from A remarkable new species of Micropeza Meigen (Diptera: Micropezidae) from Caatinga biome, Brazil. 39299 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 43 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 209 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 4 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 1803 records from AMAPPS Northeast Aerial Cruise Summer 2016. 895 records from Geometridae de France métropolitaine. 238 records from Vegetación asociada a la ciénaga de Bete, municipio del Medio Atrato, Chocó 2008. 16 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 3344 records from Leicestershire and Rutland Aculeate Records. 7 records from First record of the genus Agnara (Isopoda: Oniscidea) from Iran with descriptions of two new species. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 14 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 16618 records from Suivi Temporel des Libellules (STELI). 1 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 2 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 653 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 1290 records from Diversity of Spiders from Azorean Trails. 70 records from Ensemble des données Orthoptères. 5392 records from United Kingdom National Whale Stranding Database 1913-2008. 1 records from The bees of Lebanon (Hymenoptera: Apoidea: Anthophila). 10354 records from Inventaire de la flore de Charente-Maritime 2018. 4 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 44 records from Oman 2008: Olive Ridley Turtles of Masirah (aggregated per 1-degree cell). 4 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 8 records from A New Perlodes Species And Its Subspecies From The Balkan Peninsula (Plecoptera: Perlodidae). 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 2808 records from Natura 2000 Vallée de la Seille. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 19054 records from IMPACT OF SAHARAN DUST DEPOSITION ON BACTERIOPLANKTON IN MARINE SURFACE WATER. 63085 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 6176 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1785 records from 3Soil16S. 2 records from New and interesting palpigrades (Arachnida, Palpigradi) of the genera Koeneniodes Silvestri, 1913 and Prokoenenia Börner, 1901 from Asia. 792 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases: Cliff-nesting Birds, priority conservation species: Complementary Observations - [2010-2014]. 16 records from Sunshine Coast Council Turtle Tracking (aggregated per 1-degree cell). 7 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 92 records from Protozoa Abundance_Microbial Parameters. 482 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 1711 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 10000 records from 2020_biodiversity_information_specimen. 1467 records from Upper Silesian Museum, Bird Observations. 39 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 1075 records from Données naturalistes de Quentin ROME. 758 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 209 records from SEWBReC Springtails and allies (South East Wales). 8 records from Four new species of Phrynus, Lamarck (Arachnida: Amblypygi) from Mexico. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 5969 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgelände. 370 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2007. 676 records from National Museum of Natural Science. 231 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 165 records from Diversidad de anfibios en tres coberturas vegetales y su relación con actividades antrópicas (amenazas) presentes en el Parque Nacional Natural Tatamá y su área de influencia.. 242 records from Agencement temporel des populations et des peuplements d'invertébrés benthiques. 237 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 69 records from Global Ocean Sampling Expedition. 69 records from BIRDRACE Pfeifenten. 26 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 39 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 146 records from Données de la naturaliste Laurence Beauchamp. 164 records from Ladybirds of Ireland. 2 records from Collections ichtyologiques et herpétologiques (BOUM). 3 records from A new madicolous species of Nilotanypus Kieffer (Diptera: Chironomidae) from Amazon region, northwestern Brazil. 8929 records from Données naturalistes de Bruno OGER. 3869 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 3 records from First record of the genus Tanaostigma (Hymenopteraı Chalcidoideaı Tanaostigmatidae) from the Afrotropical region with description of three new species. 13 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 686 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 1015 records from Migration and foraging ecology of Greater Shearwater (aggregated per 1-degree cell). 82 records from Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Sarcocheilichthys vittatus, a new species of gudgeon (Teleostei: Cyprinidae) from the Poyang Lake Basin in Jiangxi Province, South China. 679 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 10 records from Hydraena (s.str.) dinarica, new species (Coleoptera: Hydraenidae) along with further records of Hydraena spp. from Durmitor National Park, Montenegro and comments on the DNA barcoding problem with the genus. 1438 records from Alien plants of Sterlitamak. 6 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 76 records from BIRDRACE Nachtigallen. 1284 records from ConDidact Citizen Science Surveys - Amphibians 2007. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 4 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 13 records from Données naturalistes de THÉVENOT Jessica. 250 records from Deep Sea fishes (Chondrichthyes, Osteichthyes) in the Southwestern Colombian Caribbean. 35074 records from Inventaire de la flore de Lot-et-Garonne 2017. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 454 records from Catalogue and description of the coccolithophores (Haptophyta, Coccolithophyceae), calcareous, scale-bearing microalgae, in New Zealand waters. 23136 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 11 records from New species, synonymy and records of Endomia and Stenidius (Coleoptera: Anthicidae) from Asia. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 21 records from Birds Specimens of Akita Prefectural Museum. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 100 records from Données naturalistes de LE GLOANEC Vincent. 3 records from Epiproct And Dorsal Process Structure In The Allocapnia Forbesi Frison, A. Pygmaea (Burmeister), And A. Rickeri Frison Species Groups (Plecoptera: Capniidae), And Inclusion Of A. Minima (Newport) In A New Species Group. 11 records from New insights into polyphyly of the harpacticoid genus Delavalia (Crustacea, Copepoda) through morphological and molecular study of an unprecedented diversity of sympatric species in a small South Korean bay. 3069 records from ERBG AVH data. 49795 records from CABI Africa Invasive and Alien Species data. 30910 records from River Biologists' Database (EPA). 230 records from Biometría peces Parque Nacional Natural La Paya. 19292 records from Tiroler Landesmuseum Ferdinandeum. 64 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile. 16 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 13868 records from Données faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 7056 records from Odonata records from RSPB Reserves 1970-2009. 850 records from Données supplémentaires Atlas des Mammifères marins. 53 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 7 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 18 records from Anfibios presentes en el Cerro Jánano. 2 records from Two new species of the genus Malayepipona Giordani Soika (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with updated key to all recognised species. 120 records from Données espèces - Expertise IPE 79. 1162941 records from NBIS Records to December 2016. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 24 records from Happywhale - Risso's Dolphin in North Atlantic Ocean. 6 records from Two new species and records of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae) from southeastern China. 1 records from Thraulodes marianoi sp. nov., a remarkable new species of mayfly (Ephemeroptera Leptophlebiidae) with dark wings from the southern Brazilian Atlantic Forest. 2060 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 2590 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 233 records from South American Antarctic Marine Biodiversity Literature. 1 records from Tibetyrus gen. nov., a new myrmecophilous Tyrini from Xizang, China (Coleoptera: Staphylinidae: Pselaphinae). 12423 records from A grid database on vascular plant distribution in the Meshchersky National Park, Ryazan Oblast, Russia. 81 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 32 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 2 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 308 records from Naturmiljø Bergensbanen 2015 (project number 616033). 1930 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 17 records from Thirteen new records of ferns from Brazil. 200 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 804 records from Happywhale - Leopard seal in Southern Ocean. 558 records from SOCAL FZN4 Marine Mammal Aerial Monitoring 2013. 82 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 3 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 3 records from Hurleyella, a new genus of Nearctic Dolichopodidae (Diptera). 4465 records from NE Scotland other invertebrate records 1800-2010. 25 records from Base de données en ligne d'observations naturalistes de mammifères marins. GEPOG & LPO. 16 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 98 records from Données opportunistes sur les odonates. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 285 records from Census of animals species through Benin from 2011 to 2019. 5 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 11 records from 2017 Onwards Rare Invertebrates in the Cairngorms Shining Guest Ant Survey Data. 16 records from Hazel Dormouse in Ireland. 27 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 6 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 954 records from NW Pacific Deep-sea Benthos Biodiversity (Beneficial Project). 51870 records from Insects, Outer Hebrides. 1 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 46 records from An der Ohm, (Wettsaasen). 48 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 568 records from Philippine Mollusk Symbiont - ICBG Collection. 185 records from Inventaire des odonates d'intérêt communautaire. 4 records from Sonerila konkanensis (Melastomataceae), a new species from South Goa, India. 3 records from Manx Basking Shark Watch 2017-2018 (aggregated per 1-degree cell). 149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 11 records from Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) of Iran and adjacent territories. 259 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 6492 records from BioGIS - Vascular plants - Israeli Gene Bank. 2418 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 7 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 4 records from Review the bamboo-feeding genus Arcofaciella Fennah, 1956 (Hemiptera: Fulgoromorpha: Delphacidae) with description of a new species from India. 1 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 115 records from Israel Sea Turtle Tracking Project 2008: Loggerhead & Green Turtles (aggregated per 1-degree cell). 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 191 records from University of Cincinnati, Margaret H. Fulford Herbarium - Lichens. 2 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 1 records from Acantorna-a new genus of Hymedesmiidae (Porifera, Demospongiae Poecilosclerida) from the western Aleutian Islands of Alaska with description of Acantorna tahoma n. sp.. 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 8705 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 402 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 31 records from HRC SCC Vessel-Based Monitoring Surveys February 2010. 2 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 488 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 673 records from Vascular plants occurrences in Dokdo islands, Korea, based on herbarium collections and legacy botanical literature. 3 records from ALLIUM (AMARYLLIDACEAE) SPECIES IN PAKISTAN: TWO NEW RECORDS AND A NEW SPECIES FROM ZHOB (BALOCHISTAN). 75 records from Happywhale - Bryde's whale in South Atlantic Ocean. 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 121 records from Registros de dípteros asociados al proyecto: Estratificación espacial del dengue basado en la identificación de factores de riesgo en el departamento del Cauca. 985 records from Marine Turtles. 65 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 81 records from Gabon 2009-10: Pongara, Leatherback Turtles (aggregated per 1-degree cell). 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 3 records from Two new species of the genus Tylostega Meyrick, 1894 (Lepidoptera: Crambidae) from China, with a list of all the known species in the world. 240 records from Evaluación del macrobentos de la plataforma continental del Caribe colombiano. 38 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 2 records from Results of palynological analysis of Hole 302-M0004C. 4722 records from Atlas of Bats from Continental Portugal 2013. 1252 records from Censos de aves en los municipios de Honda (Tolima) y Guaduas (Cundinamarca) - BIO Alas, cantos y colores. 42968 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 3 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 68 records from Streuobstwiese. 3455 records from SIM-Fungal records compiled by Joan Montón. 64848 records from Western Australian Museum provider for OZCAM. 27 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 247 records from Flora vascular y no vascular: expedición Cuenca Media del río Chicamocha - Proyecto Boyacá BIO UPTC. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 1107454 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 1 records from Description of a new species of the Melanorivulus pictus species-group (Cyprinodontiformes: Rivulidae) from the Rio Paraná basin in Brazil. 27202 records from NRW Regional Data: South East Wales Non-sensitive species. 2 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 47 records from Marine Turtle Conservation Project 2012-2013 (aggregated per 1-degree cell). 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 709 records from (Appendix Table 3) Relative abundances of planktonic foraminiferal species in sediment core MD01-2390. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 6 records from Virotia azurea (Proteaceae: Macadamieae), a striking new species endemic to New Caledonia and notes on V. francii and V. leptophylla. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 1 records from Taxonomic novelties in Apocynaceae subfam. Asclepiadoideae from New Caledonia. 227 records from CEPEC herbarium - Centro de Pesquisas do Cacau - Herbário Virtual REFLORA. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 4616 records from Inventaire de la flore du Grand Poitiers 2009. 33 records from Waldstück am Schullandheim Bad Bederkesa. 10 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 334 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 3150 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1 records from Données naturalistes d'Olivier DELZONS. 140 records from Naturalis Biodiversity Center (NL) - Diptera. 72 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 164 records from Schulhof Gymnasium Hürth Bonnstrasse. 6 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 174 records from BIRDRACE Bon(n)apartemöwen. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 16 records from Plant-parasitic nematodes of Republic of Karelia. 1545 records from NatureMap Calcrete Survey. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 1 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 1 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 15 records from Six new species of Orthochirus Karsch, 1892 from Iran (Scorpiones Buthidae). 2465 records from Elaboration de table de tarif de cubage multispécifique (I). 3 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 88 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 30 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 3 records from Vasopora ceramica n. gen., n. sp. - a new abyssal cyclostome bryozoan from polymetallic nodules in the Russian exploration area, Clarion-Clipperton Fracture Zone, eastern Pacific Ocean. 158 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 16 records from Insect Collections of Okomu National Park- Nigeria. 78232 records from University of Minnesota Insect Collection. 103513 records from ARABEL - Arachnologia Belgica. 173 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 412 records from Heinersdorfer Sumpfwiese. 8 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 4224 records from Arctic Species Trend Index (ASTI) : Marine. 30 records from Ohio Wesleyan University Mammal Specimens (Arctos). 5869 records from Wolli Creek Preservation Society Bird Survey. 63 records from Inventaire des espèces végétales de la vallée de Gounti Yéna (Niamey). 320 records from MLZ Bird Collection (Arctos). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 10 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 126 records from Naturschutzgebiet Müchelholz (Mücheln). 166 records from Wiese am Waldrand (Gurtweil). 1 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 403 records from NMML Gulf of Alaska marine mammal survey 2003. 2592 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 39 records from Northern Cyprus 2010 (aggregated per 1-degree cell). 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 1 records from Description of a new species of Megischus Brulle (Hymenoptera, Stephanidae), with a key to the species from China. 5 records from The species of the bee genus Centris of the “ hyptidis group ” revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini). 3 records from A new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Tamil Nadu, Southern India. 3 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 6 records from Vermont Orthoptera Records from Historic Dot Maps. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 423 records from Colección de Bacterias del Museo de Historia Natural Marina de Colombia – Makuriwa (Invemar). 2 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 1839 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 267 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 2 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 5 records from Integrative description of new giant pill-millipedes from southern Thailand (Diplopoda, Sphaerotheriida, Zephroniidae). 5 records from New species of Culex (Culiciomyia) (Diptera: Culicidae) from Talangaye Forest in Cameroon and descriptions and identification keys for males of the Afrotropical species of the subgenus. 2 records from Marine algal (seaweed) flora of Faial Island, Azores. 101 records from Naturgrundstück (Eutin). 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 11 records from SNI California Sea Lions 2014 (aggregated per 1-degree cell). 166 records from données araneologiques de LEENKNEGT Virginie. 3500 records from Pelagic sediment metagenome of Gulf of Kutch. 4 records from Herbarium Senckenbergianum (FR) - Protista. 1541 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 1 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 23 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 38418 records from Données de l'Observatoire de la Faune de Bourgogne. 3044 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 2 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 131 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 89 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 392 records from Hawthorne Canal Birdwatching Survey. 1207 records from Microbial diversity studies of Arabian Sea sediment. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 190 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 177 records from Echinoderms from the Seaflower Biosphere Reserve. 24 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 31385 records from Allan Herbarium (CHR). 368 records from Biological Recording in Scotland - Bumblebee Survey. 19688 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 7 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 34 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 15 records from Two new sympatric species of Stenocercus (Squamata: Iguania) from the inter- Andean valley of the Mantaro River, Peru. 27 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 205 records from CRC HRC Shore-based Surveys KB11 2013-2015. 4166 records from Línea base general de hormigas para el valle medio del Magdalena - VMM. 1 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 299 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 251 records from Données naturalistes d'Olivier LAURENT. 22728 records from Restauración y conservación de Isla Guadalupe. 11 records from Coleção de Coleoptera da Universidade de Brasília. 345 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 45 records from Natterjack Toads of Ireland. 98 records from Warnowtal (Rostock). 22 records from Site Condition Monitoring of dragonflies on Loch aí Mhuilinn SSSI potential extension - 2016. 2 records from The first record of the family Chloroperlidae (Plecoptera) from the Guangxi Zhuang Autonomous Region of southern China, with description of a new species of Sweltsa Ricker, 1943. 124 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 6 records from Wuhle - Brücke / B1. 3 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 2260 records from Marie-Victorin Herbarium (MT) - Bryophytes. 60 records from Individuos de Gunnera schultesii L.E.Mora y su respuesta al efecto de la sombra y el tipo de fertilizante sobre su crecimiento en condiciones ex situ. 10 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 27 records from CNMI Sea Turtle Program satellite tracked green turtles 2011. 1 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 382 records from Poliquetos fondos arenosos de Arrecifes de Coral en el PN Archipiélago de Los Roques, Venezuela. 386063 records from Compost microbe establishment and growth in agricultural soils. 13 records from Bostryx tortoranus (Doering, 1879) species complex (Gastropoda: Stylommatophora: Bulimulidae), a review of taxonomy and distribution of endemic species from Argentina. 59436 records from National Benthic Inventory. 5 records from New records of two butterflies of the genus Polyommatus Latreille, 1804 (subgenus Agrodiaetus Hübner, 1822) (Lepidoptera: Lycaenidae) from Iraq. 358 records from Comunidad fitoplanctónica presente en la Bahía de Buenaventura 2018. 25 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 953 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 8 records from Abundant box jellyfish, Chironex sp. (Cnidaria: Cubozoa: Chirodropidae), discovered at depths of over 50 m on western Australian coastal reefs. 11 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 3 records from Happywhale - Adelie Penguin in Southern Ocean. 55457 records from MDFRC macroinvertebrate survey. 132 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 62 records from Amtsrain Apolda-Zottelstedt. 128 records from Inventaire des reptiles 2014. 1 records from A new species of genus Oxytauchira from India (Orthoptera: Acrididae). 583 records from MoJ BioBlitz August 2018. 29354 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 31 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 15 records from A New Species Of Isoperla Banks (Plecoptera: Perlodidae) From The Southern Appalachians, With Notes On The I. Montana Group. 1134 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 6 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 1 records from West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae). 46 records from Fauna anfibia asociada al bosque del resguardo indígena Cuti, municipio de Unguía, Chocó. 2020. 20440 records from Inventaire de la flore de Charente-Maritime 2017. 36 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 4853 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 99 records from Dorfrand Mauderode. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 61 records from Shrews of Poland. 8 records from Archaeal 16S Ribosomal RNA RefSeq Targeted Loci Project. 1 records from Checklist and a new species of Lippia (Verbenaceae) from the Diamantina Plateau, Minas Gerais, Brazil. 5592 records from K-State Museum of Entomological and Prairie Arthropod Research. 18 records from Bonaire Turtle Tracking 2012 (aggregated per 1-degree cell). 4 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 9535 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 51 records from Monitoreo hidrobiológico en el Río Aures para el tramo de influencia de la central Aures Bajo. 70 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 3 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 144 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 31 records from STELI 2015 Saint-Pée-sur-Nivelle (64) par l'association EcoGIS. 5229 records from European Moth Nights. 851 records from The Dolphin Project. 172 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 19 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 6775 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 542 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 12 records from A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes: Heptapteridae) from the Orinoco River basin. 12593 records from Données Entomologiques A. HORELLOU 1988-2018. 2 records from A new species of Paralithoxus (Siluriformes: Loricariidae: Ancistrini) from the highlands of Serra da Mocidade, Roraima State, Brazilian Amazon. 285 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 632 records from 2019_NSMK_PL. 48 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1346 records from Records of Halicarcinus planatus at sub-Antarctic regions. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 1627 records from Herbier National de Guinée (HNG). 5 records from New records of Stenopygium Becker (Diptera: Dolichopodidae) from the Neotropical Region, and a key to species. 861 records from Iowa State University Fishes Collection. 404 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 3 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 455 records from EDIT - ATBI in Gemer area (Slovakia). 19860 records from Global compendium of Aedes albopictus occurrence. 325 records from Inventaire malacologique de la RNR des Marais de Stors. 596 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 88 records from Teich Berlin Wuhlheide. 2 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 41 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 5 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 150 records from AKG-Gelände (Bensheim). 3333 records from WOLL AVH data. 206 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 354 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 15 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 426 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 2138 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 16858 records from Colección de Peces de Agua Dulce del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 35 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 3 records from Three new species of the subterranean genus Guiodytes from Guangxi, China (Coleoptera: Carabidae: Clivinini). 92 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 858 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 1 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 210 records from Lebensraum Gesamtschule (Langerwehe). 5 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 2489 records from Données des collections d'algues du MNHN. 1515 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 478 records from Coléoptères Silphidés du département du Loiret. 51 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 2 records from Two remarkable new species of oribatid mites (Acari: Oribatida) from Acacia litter of Kerala, India. 163857 records from NOAA AFSC North Pacific Groundfish Observer. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 1 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 31150 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 177 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 2 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 67797 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 414 records from Etude floristique de la forêt marécageuse de Lokoli au Bénin. 84 records from Marine algal (seaweed) flora of São Jorge Island, Azores. 1036 records from BUND - Dassower See (Lübeck/Dassow). 5 records from A northern range extension of a Canadian species of Special Concern, Dielis pilipes (Hymenoptera: Scoliidae), in the Okanagan Valley of British Columbia. 48111 records from Données naturalistes de Monsieur François FOURNIER. 346 records from Birds and plant species near Petushki town (Vladimir region). 1 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 30484 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 9 records from Jeu de données convention FEGVE-SPN (numéro 2). 4 records from Two new species of the genus Deltomerodes Deuve, 1992 (Coleoptera, Carabidae, Patrobini) from Xizang, China. 4 records from Sächsische Schweiz (Wehlener Gebiet). 11 records from A review of the Asian orb weaving spider genus Pronoides (Araneae: Araneidae). 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 343 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 6067 records from Arthur Chapman Observations. 5 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 571 records from Cuxhavener Küstenheiden. 1479718 records from Hatikka Observation Database. 553 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 751 records from Données naturalistes de Monsieur JOURDE Rémi. 62 records from Rainforest and cloud forest Scolytodes (Curculionidae, Scolytinae, Hexacolini) from the Arthropods of La Selva inventory in Costa Rica: new species, new synonymy, new records. 15 records from Suivi de la colonie de Pipistrelles de la Petite Ceinture à Paris. 21 records from Riedkanal Bötzingen. 1 records from New record of the genus Baetiella Uéno, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 54 records from Aves marinas del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 141 records from Herbario del Museo de Historia Natural C.J. Marinkelle. 2 records from A new record of the family Isonychiidae (Insecta: Ephemeroptera) from the Western Ghats, India with a description of new species. 5 records from Seven new species and additional records of Palaearctic Leptusa, primarily from Yunnan, China (Coleoptera: Staphylinidae: Aleocharinae). 256 records from Oceanic Society's Marine Mammal Sightings in Belize 1992 - 2011. 32 records from Invasive alien species Noccaea caerulescens (J. Presl & C. Presl) F. K. Mey. in the Republic of Karelia. 52 records from Distribution of Aureoboletus projectellus in Europe. 445 records from Enrichment metagenome. 4 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 12855 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 1115786 records from Dragonfly records from the British Dragonfly Society Recording Scheme. 1131 records from eDNA_Subseafloor. 2 records from A new species of Hypsohapsis (Heteroptera: Schizopteridae: Hypselosomatinae) from the Brazilian Amazon. 61 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes (Crustáceos). 637 records from Colección de macroalgas de la costa Argentina (IADO-UNS-CONICET). 12273 records from Invasive Plant Atlas of the MidSouth (IPAMS). 3 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 11 records from Records Of Neoperlini (Plecoptera: Perlidae) From Brunei Darussalam And Sarawak, With Descriptions Of New Phanoperla Banks And Neoperla Needham Species. 12 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 1 records from Happywhale - Indian Ocean bottlenose dolphin in Indian Ocean. 2660 records from Biodiversity of the Desna river valley and its tributaries. 1361 records from Códigos de barras de la vida en peces y zooplancton de México. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 2 records from Tertiarius minutulus sp. nov. (Stephanodiscaceae, Bacillariophyta) - a new fossil diatom species from Lake Ohrid. 37 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 2 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 1 records from A new species of Casmaria H. Adams & A. Adams, 1853 (Gastropoda, Cassidae) from the Philippines identified by molecular data. 1718 records from Fish of the Recherche Archipelago , Western Australia (2002). 5 records from Loricifera - SMF. 20 records from Morphological phylogenetic analyses and taxonomic revision of the Panorpa davidi group (Mecoptera: Panorpidae). 833 records from Plant species from the sacred and community forests of Mono departement. 149164 records from KTP Ring Data. 39 records from Revision of the spider genus Mystaria Simon, 1895 (Araneae: Thomisidae) and the description of a new genus from the Afrotropical region. 580 records from Colección Ornitológica-Museo de Historia Natural Unillanos. 3 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 11 records from Données d'observation opportunistes collectées durant la campagne de prélèvements sédimentaires SHELL/CREOCEAN en Guyane française en 2013. Shell Exploration and Production France. 1700 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 16 records from Subspecies of Pleurota bicostella (Clerck, 1759) revisited and descriptions of nine new species in the P. bicostella species group (Lepidoptera: Gelechioidea Oecophoridae: Pleurotinae). 1422 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 1 records from Two new genera and species of Fidicinini Distant, 1905 with a re-description of Nosola Stål, 1866 (Hemiptera, Auchenorrhyncha, Cicadidae). 12118 records from Soil metagenome from healthy and unhealthy agricultural soil. 2 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 2 records from New state and island records of Coccinellidae (Coleoptera) in Hawai‘i, USA. 2 records from Brown University Herbarium. 89 records from Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 19317 records from Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 5 records from Satellite Tracking of Hawksbill Turtle in West Sumbawa, Indonesia (aggregated per 1-degree cell). 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 7 records from Four new species of Diptilomiopinae from China (Acari: Eriophyoidea: Diptilomiopidae). 62 records from Siphonaptera and Phthiraptera Recording Scheme - records verified via iRecord. 59 records from Schulgelände SGD/Viersen. 759 records from Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 48 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 10692 records from TOPP Summary of SSM-derived Telemetry. 4 records from Colección Palinológica del Herbario LIL (PAL-TUC-FML-Tucumán). 35 records from Leopard and Weddell seal program 1999/2002. 1 records from A new species and southernmost record of Cestrus Townes (Hymenoptera Ichneumonidae, Cryptinae). 4707 records from Données naturalistes de Ségolène FAUSTEN. 54 records from Distribución, abundancia y efectos nocivos de tres especies de plantas invasoras (Oeceoclades_bonampak). 2 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 2 records from New records of phytoseiid mites from Mauritius Island (Acari: Mesostigmata. 396 records from Mushrooms Flora of Nepal at Central Department of Botany, Tribhuvan University, Nepal. 935 records from MZL Invertebrate Collections. 12 records from Two New Species Of Dictyogenus Klapálek, 1904 (Plecoptera: Perlodidae) From The Jura Mountains Of France And Switzerland, And From The French Vercors And Chartreuse Massifs. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 4 records from Four new species of Xiphocentron Brauer, 1870 (Trichoptera: Xiphocentronidae) from the Atlantic Forest, southeastern Brazil. 173 records from Invertebrates of the river Tana Basin in Kenya available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section. 352 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 74 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 8 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 1 records from Karpfenteich, Klasse 6d. 2 records from Redescription of Stilobezzia (Stilobezzia) albicoxa Lane & Forattini, 1956 with new synonymy (Diptera: Ceratopogonidae). 485 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 1 records from Gastrodia qingyunshanensis (Orchidaceae: Epidendroideae) - a new holomycotrophic orchid from Guangdong, China. 28 records from Revision of New World Cosmorrhyncha Meyrick, 1913 (Lepidoptera: Tortricidae: Olethreutinae), with descriptions of five new species. 2 records from Unveiling the morphology of the Oriental rare monotypic ant genus Opamyrma YAMANE, BUI & EGUCHI, 2008 (Hymenoptera: Formicidae: Leptanillinae) and its evolutionary implications, with first descriptions of the male, larva, tentorium, and sting apparatus. 160 records from Acquario di Genova, Delfini Metropolitani Project, cetacean sightings 2001-2009. 645 records from Ensemble des données Rhopalocères. 362 records from Seabird temporal composition, abundance and habitat use in “Punta La Metalera” (Arequipa), Southern Peru. 5 records from The InBIO Barcoding Initiative Database: DNA Barcoding reveals sexual dimorphism in Isotrias penedana Trematerra, 2013 (Lepidoptera: Tortricidae, Chlidanotinae). 15 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 1 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 4743 records from Ethnobotanical surveys species in Benin (West Africa). 17 records from Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae). 5576 records from uncultured prokaryote Targeted loci environmental. 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 136 records from Inventaire faunistique de l'ENS des Parc des berges de Seine. 1826 records from Soil invertebrates occurrences in European North-East of Russia. 3 records from Novedades taxonómicas en Campanulaceae neotropicales I: dos nuevas especies de Centropogon C. Presl de Venezuela. 111 records from BIRDRACE Die Wendehälse. 172 records from SEFSC GoMMAPPS Vessel Survey 2018 Summer. 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 739 records from Intermountain Herbarium (fungi, not lichens), Utah State University. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 11367 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 657 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 1 records from Dressed in black. A New Ansonia Stoliczka, 1870 (Lissamphibia: Anura: Bufonidae) from Gunung Murud, Sarawak, East Malaysia (Borneo). 42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 1591 records from Ornithological observations in the Kharkiv region of Ukraine. 19859 records from CAS Entomology (ENT). 178200 records from Carnet B Lorraine. 22 records from Naturalis Biodiversity Center (NL) - Pisces. 5 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 5 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 153 records from Myxomycetes collection of the University of Eastern Finland. 61751 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 370817 records from Seasearch Marine Surveys in England. 20 records from New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda). 53 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 5 records from The Endemic Sulawesi Fish Genus Lagusia (Teleostei: Terapontidae). 7 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 308 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 48 records from Swiss Occurrence Records of Native Species of Various Faunal Groups. 15 records from The genus Stenoterommata Holmberg, 1881 (Araneae, Pycnothelidae) in the Cerrado and Atlantic Forest from Southeastern and Central Brazil: description of four new species. 172 records from Collection Trichoptera - SMF. 11 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 162 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 6 records from Happywhale - Arnoux's Beaked Whale in Southern Ocean. 115 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 2540 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 18106 records from Arizona State University Hasbrouck Insect Collection. 2536 records from Invasive Alien Species Occurrence in Ghana. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 1618 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 29 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 156514 records from Queensland Museum provider for OZCAM. 2 records from A taxonomic reappraisal of the Smooth Slug Snake Asthenodipsas laevis (Boie, 1827) (Squamata: Pareidae) in Borneo with the description of two new species. 6387 records from Données naturalistes de Monsieur LAFAGE Denis. 5 records from On the genera Ptiloneura Enderlein, Loneura Navás, and Loneuroides García Aldrete (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 8 records from IPAE egg clutches collection (Aves). 18 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 1 records from Molche in Ruschwedel. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 13 records from A review of the bats (Chiroptera) of the Republic of Congo, including eight species new to the country. 7220 records from Données d'observations d'orthoptères en Auvergne, d'Emmanuel Boitier, de 1998 à 2015.. 5 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 157 records from Herpetofauna and other animals registered within Rzhyshchiv city amalgamated territorieal community (CATC) (Kyiv region) in 2021. 20 records from Actualización de la base de datos de la Colección nacional mexicana de cultivos microbianos. 15 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 700 records from Données naturalistes d'Arnaud LE NEVÉ. 1 records from A review of New World Malaxa (Hemiptera: Fulgoroidea: Delphacidae). 4307 records from Biomass and mortmass of woody vegetation in metal-contaminated areas (Southern Urals, Russia). 374 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 6 records from A review of Solierella Spinola, 1851 (Hymenoptera, Crabronidae) from Iran with description of four new species. 199 records from Happywhale - Leopard seal in South Atlantic Ocean. 717 records from Redland City Council Citizen Science Portal. 264 records from HBRG Invasive Non-native Plants Dataset. 239 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 4 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 52 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 653 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 1 records from Lisubatrus dongzhiweii gen. et sp. nov. from the Gaoligong Mountains, China (Coleoptera: Staphylinidae: Pselaphinae). 342 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 1 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 7114 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 229 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 3 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 5 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 1 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 34 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 718 records from Bird species occurrences recorded from selected sites in mid Tana River Basin, Kenya. 143568 records from Movement patterns of Peruvian Boobies off Isla Lobos de Tierra 2006. 368 records from Données du naturaliste PROVOST romain provenant de la base de donnée du SINP Île-de-France CETTIA. 13545 records from Temporal dynamics of bacterioplankton community in response to excessive nitrate loading in the oligotrophic coastal water. 93 records from Wildlife Sightings in the City of Logan. 199 records from Birds Specimens. 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 94 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : données espèces non cibles piégées. 592 records from Caracterización de Fauna del Banco de Hábitat del Bosque Seco Tropical Antioquia de Terrasos. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 86 records from Fliegenhaupt Marksuhl. 3 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 9854 records from DMNS Mammal Collection (Arctos). 2199 records from Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 1 records from A new species of the genus Pachytriton (Caudata: Salamandridae) from Hunan and Guangxi, southeastern China. 216 records from (Table 2) Stable oxygen and carbon data, and relative abundances of selected planktonic foraminiferal species in the surface sediment samples retrieved during the SO-189 cruise off W Sumatra. 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 66 records from Tortugas Marinas del Golfo de California (aggregated per 1-degree cell). 58 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 64 records from Bats of northeastern Vietnam. 1028 records from IBF Monitoring of Fungi. 11 records from A New Species Of Capnia Pictet, 1841 (Plecoptera: Capniidae) From Kyushu, Japan, With Description Of Male Drumming Signals. 4 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 1 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 742 records from Pacific turtle tracks: Turtle-Safe Seas Project. 5 records from New data on jumping spiders of Iran, with a new species of Salticus (Araneae: Salticidae). 117 records from Programme de valorisation des zones humides chassées - volet Amphibiens. 3018 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 27 records from Caracterización floristica del Alto del Buey, Bahia Solano - Chocó. 11 records from New and little-known sun-moth species from Australia (Lepidoptera, Castniidae). 1 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 75 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 70 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 2 records from A new crab-associated amphipod of the genus Isaeopsis Barnard, 1916 (Amphipoda Senticaudata: Ischyroceridae) from southern Chile. 240 records from Knechtweide (Kohlfurth). 22 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 83 records from MCP-Mamiferos - Coleção de Mamíferos. 1 records from The Echinoderm Fauna of the Azores (NE Atlantic Ocean). 358 records from Données du Syndicat de la Vallée de l'Orge Aval (SIVOA). 781 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 2 records from Two new species of Helicopsyche Siebold 1856 (Insecta: Trichoptera: Helicopsychidae) from Pará State, northern Brazil. 11671102 records from The Danish Environmental Portal, species and habitats-database "Danmarks Miljøportals Naturdatabase". 19 records from EDP Foz-Tua: Nocturnal Birds - Complementary Studies [2010]. 1 records from New names for two Malagasy species of Canarium L. (Burseraceae). 29 records from Phenological Center - Mushrooms (Karelia). 415 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 13990 records from Tachinid Recording Scheme - GB and Ireland records. 9 records from A Taxonomic Review of the Trapdoor Spider Genus Myrmekiaphila (Araneae, Mygalomorphae, Cyrtaucheniidae). 5 records from Thoridae (Crustacea: Decapoda) can penetrate the Abyss: a new species of Lebbeus from the Sea of Okhotsk, representing the deepest record of the family. 3 records from Denitrification bacteria in sediment cores of Daya Bay, China. 6 records from Five new species of Nazeris Fauvel in Guangxi, China (Coleoptera, Staphylinidae, Paederinae). 5 records from Données naturalistes de Mikaël PAILLET. 9 records from A review of bat research in Thailand with eight new species records for the country. 4379 records from Wild Bee Specimens from Blueberry and Raspberry Farms in the Champlain Valley, Vermont, USA. 4607 records from Données de type contact en Guadeloupe. 121 records from HUCP herbarium - Pontífica Universidade Católica do Paraná PUC - Herbário Virtual Reflora. 451 records from The Sphecid Wasps of the genus Cerceris L, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from the Palearctic Region (part II). (Hymenoptera, Apoidea, Crabronidae). 4184 records from Flora superior del Bosque Seco Tropical presente en 10 parcelas ubicadas en el Valle del Cauca. 87 records from Microzooplankton abundance measured on water bottle samples at station PS65/570-4. 5772 records from A grid-based database on vascular plant distribution in Samoylovsky District of Saratov Oblast, Russia. 6954 records from IRKU Herbarium: collections of vascular plants. 1 records from Description Of Etrocorema Belumensis Sp. N. From Royal Belum State Park, Perak, Malaysia. 6 records from New and little known species of Eumolpinae (Coleoptera: Chrysomelidae) from Northern Vietnam. 3 records from A new, uniquely patterned spiny eel (Teleostei: Mastacembelidae) from southern Borneo, Kalimantan Tengah, Indonesia. 55 records from Galls on Beech Trees in Hainich, 2008. 15 records from Three new species of Holoscolex (Clitellata, Glossoscolecidae) from the Gurupi Biological Reserve, last forest remnant of the Belém Endemism Area, Eastern Amazon. 6 records from New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus. 1596 records from Microbial communities in deep eastern Mediterranean Sea surface sediments. 2053 records from Atlas des Poissons et Crustacés d'eau douce de Guadeloupe. 4019 records from Inventario multitaxonómico del ANP Médanos de Samalayuca. 31 records from Ecosystems of the sandstone region incl. sand-belt (SE of Melb.). 1037 records from Evaluación del estado actual de las poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en los municipios de Paz de Ariporo y Hato Corozal, Casanare. 4 records from The Chinese species of the mealybug genus Neotrionymus Borchsenius (Hemiptera: Coccoidea: Pseudococcidae). 8 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 1 records from Catharanthus makayensis L. Allorge, Phillipson & Razakamal. (Apocynaceae), a new species from Madagascar. 17710 records from inatura - Erlebnis Naturschau Dornbirn. 14 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 4 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 93 records from ProDelphinus Peru Leatherback Tracking Project (aggregated per 1-degree cell). 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 4 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 95 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 17 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 16 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 110418 records from Happywhale - Humpback Whale in North Pacific Ocean. 712 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 194 records from CNAC/Coleccion Nacional de Acaros. 2043 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 24 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 53 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 1 records from A new cave-dwelling Gekko (Gekko) from Lopburi Province, central Thailand (Squamata, Gekkonidae). 8 records from The millipede genus Tylopus Jeekel, 1968 (Diplopoda, Polydesmida, Paradoxosomatidae), with a key and descriptions of eight new species from Indochina. 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 22771 records from INVESTIGATING THE MICROBIAL EUKARYOTIC COMMUNITIES IN THE SURFACE WATERS OF THE ARAFURA SEA AND CORAL SEA. 1824 records from TransForest - vegetation, lichen and fungi data 2016. 3 records from Otacilia fansipan spec. nov., the second congener recorded from Vietnam (Arachnida: Araneae: Phrurolithidae). 6 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 1 records from A new species of Liphistius from Myanmar and description of the actual male of L. birmanicus Thorell, 1897 (Araneae, Mesothelae, Liphistiidae). 588 records from artsprosjektet_51-14_ophiostomatoid_fungi. 112 records from Microzooplankton abundance measured on water bottle samples at station PS65/466-2. 201 records from Biodiversity of springs and rock seepages 2003. 146 records from Registros de la vegetación presente en la Cienaga de Beté, Municipio del Medio Atrato, Chocó - 2018. 10776 records from CEFS_16S_ITS. 36323 records from Biowide Species data. 11 records from Inventaire et regroupement de données Natura 2000. 10 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 816 records from Línea base general de peces para el valle medio del Magdalena - VMM. 5 records from Heteragrion lencionii (Odonata: Heteragrionidae) sp. nov. from Serra de Itabaiana National Park, Northeastern Brazil. 7 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 521 records from Schanzenanlage Bergham. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 74 records from Reptiles presentes en la colección herpetológica SINCHI de la expedición al Río Apaporis - Proyecto Colombia BIO. 14 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 22 records from Contributions to the study of the grasshopper (Orthoptera: Acrididae Gomphocerinae) courtship songs from Kazakhstan and adjacent territories. 549 records from Données du Geckos vert des Hauts (Phesulma borbonica) du Parc national de La Réunion. 160 records from AVJNF: Søholt Storskov, amphibian survey. 1 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 25 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 11 records from New host-plants records of Afrotropical Gelechiidae (Lepidoptera), with description of three new species. 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 154 records from Viabilidad de semillas dispersadas por fauna en la microcuenca Teusacá, Bogotá D.C.. 757 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (Abejas). 3 records from Parochodaeus bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia gentilii (Martínez) (Coleoptera: Scarabaeidae), two species newly discovered in Chile. 238 records from Données Mammifères marins Aquasearch - Dauphin Passion. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 1459 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2009. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 31 records from Bulletin d'informations de l'Association française de Lichénologie. 1552 records from Nematoda of Costa Rica (INBio). 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 6 records from Revision of the family Acidopsidae Števčić, 2005, and the systematic position of Typhlocarcinodes Alcock, 1900, Caecopilumnus Borradaile, 1902, and Raoulia Ng, 1987, with descriptions of two new genera and five new species (Crustacea: Brachyura: Goneplacoidea). 2324 records from WTSWW Data: All Taxa (West Wales). 4 records from Two more new species of the Cyrtodactylus peguensis group (Squamata: Gekkonidae) from the fringes of the Ayeyarwady Basin, Myanmar. 56 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 37 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 500 records from CRESLI marine mammal observations from whale watch cruises 2000-2019. 2 records from Happywhale - Southern Bottlenose Whale in Southern Ocean. 312229 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 192 records from "Ahrschleife bei Altenahr". 59456 records from South Australian Museum Australia provider for OZCAM. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 1 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 12 records from New species and records of Caulleriella (Annelida, Cirratulidae) from shelf and slope depths of the Western North Atlantic Ocean. 2 records from Novelties from the Northern Mountains Complex of Madagascar IV: A new Rinorea Aubl. (Violaceae) of restricted range from the Galoko and Kalabinono massifs. 7 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 1 records from Brock University Herbarium (BU). 4303 records from Whicher Scarp Flora Survey. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 69 records from Unter hellen Zinnen und finsteren Grotten. 10167 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 2269 records from UNCW Marine Mammal Aerial Surveys 2006-2007. 1 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 55 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 2 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 6366 records from Modernisation des ZNIEFF du PnrL. 5 records from The West and Central African species of Vepris Comm. ex A. Juss. (Rutaceae) with simple or unifoliolate leaves, including two new combinations. 576 records from Zooplancton del estrecho de Bransfield y alrededores de Isla Elefante, verano austral 2019-2020, durante la VI Expedición Científica de Colombia en la Antártica. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from Dombeya sevathianii (Malvaceae): A new critically endangered species endemic to Mauritius (Indian Ocean). 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 1264 records from Grand Voyeux - Suivis scientifiques. 36 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 23 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 42 records from UWIZM Cnidarians. 1 records from Pyrrosia sarthalensis, a new species of Polypodiaceae from Kathua District, Jammu and Kashmir, Western Himalaya, India. 1 records from Planothidium galaicum sp. nov. (Bacillariophyta, Achnanthidiaceae), a new diatom species from Galician coast, Spain. 299 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 150 records from Ningaloo Outlook Whale Shark tracking (aggregated per 1-degree cell). 33814 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 109628 records from Tasmanian Museum and Art Gallery provider for OZCAM. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 4575 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 1774 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 19 records from Colección Ornitológica del Museo de Historia Natural de la Universidad de la Amazonia. 45 records from Brown bear monitoring data from Deosai National Park. 526 records from Eventos de monitoreo de la especie plaga Didymosphenia geminata en cuerpos de agua de la zona centro sur austral de Chile, Etapa I (2016 - 2017). 494 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 9 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 71490 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 602 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 2 records from A New Genus of the Spider Family Caponiidae (Araneae, Haplogynae) from the West Indies. 3704 records from Inventaire des pelouses calcicoles du PNR du Marais Poitevin 2017. 16453 records from Chrysomelidae beetle data from iRecord. 12 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT Tromsø Museum. 420 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 64903 records from 18S Monterey Bay Time Series: an eDNA data set from Monterey Bay, California, including years 2006, 2013 - 2016. 24 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 1 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 59 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 13 records from Biodiversity Surveys, South-east Arnhem Land. 55 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru. 366 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (2), 2009 - Données faune. 11 records from New species and records of the Neotropical genus Cyrnellus (Trichoptera: Polycentropodidae) and the re-establishment of C. minimus and C. marginalis. 120 records from Tejidos asociados al estado de conservación y riesgo de extinción del ensamblaje de anfibios de tres páramos colombianos. 19 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 59 records from Wichita State University Collection. 86 records from Données naturalistes de Pierre-Alexis RAULT. 195057 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 1 records from Pitcairnia albifolia (Bromeliaceae), a new species from the Talamanca Mountains in Veraguas Province, Panama. 8158 records from Dark ocean microbial diversity. 860 records from Taxa occurrences and composition of benthic macroinvertebrates from biodiversity surveys on Lake Victoria, Uganda (2001-2006). 9 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 2 records from A new species of Gamasellodes Athias-Henriot (Mesostigmata: Ascidae) from Brazil and a key to the world species of the genus. 3 records from Taxonomic review of the genus Assamacris (Orthoptera: Acrididae: Catantopinae) with a new species and a newly discovered female. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 51 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 4 records from Three new species and one new record of Torrenticolidae (Acari, Hydrachnidia) from Wuyishan with an updated key for Chinese fauna. 2 records from Ovomanonychus, a new genus of South American Sericoidini (Coleoptera Scarabaeidae: Melolonthinae). 3 records from DD_cyano Targeted loci environmental. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 7 records from Happywhale - Northern Right Whale Dolphin in North Pacific Ocean. 7 records from Genus Stathmopoda Herrich-Schäffer, 1853 (Lepidoptera: Stathmopodidae) from China: Descriptions of thirteen new species. 54 records from Anfibios y reptiles de la serranía las Quinchas, Boyacá - Proyecto Boyacá BIO. 11387 records from 16S data from: Diversity of Pico- to Mesoplankton along the 2000 km Salinity Gradient of the Baltic Sea (Hu et al. 2016). 4 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 22 records from Ahuyentamiento, rescate y reubicación de fauna en el área de influencia directa del proyecto Hidroeléctrico Mulatos II. 2 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 13 records from Coleção de Nematoda do Museu Nacional - UFRJ. 2 records from Description of a new species of deep-sea spider crab from the genus Crocydocinus Lee, Richer de Forges & Ng, 2019, from the south-eastern Arabian Sea (Crustacea Decapoda: Majoidea: Epialtidae). 6254 records from Inventory of plant species through Benin (West Africa). 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 4 records from A new species of Ephoron Williamson, 1802 (Ephemeroptera: Polymitarcyidae) from Thailand. 13 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 486 records from Données du/de la naturaliste Hasrouni Sami provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 21 records from Two new trans-Andean species of Imparfinis Eigenmann & Norris, 1900 (Siluriformes: Heptapteridae) from Colombia. 529 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 2011 records from UNCW Right Whale Aerial Surveys 2008. 5 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 2 records from A new species of Hieracium sect. Pannosa (Asteraceae) from Bulgaria. 12 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 564 records from Atewa Range Forest Reserve Bryophytes dataset, Ghana. 7 records from Description of a new species of Glassella Campos & Wicksten, 1997 from a coastal lagoon, SE Gulf of California (Crustacea, Decapoda, Pinnotheridae). 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 286 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 1735 records from Occurrence database of native plants and animals of south-central Chile. 13 records from Three new species and three new records of the genus Bamboosiella from China (Thysanoptera: Phlaeothripidae). 67477 records from Swiss National Bat Databank: Regional Coordination Western Switzerland (CCO). 4 records from Cryptic diversity across the Trans-Mexican Volcanic Belt of Mexico in the montane bunchgrass lizard Sceloporus subniger (Squamata: Phrynosomatidae). 259 records from Natura 2000 Parc naturel régional de Lorraine. 1 records from Nothobranchius nikiforovi, a new species of seasonal killifish from the lower Matandu drainage in south-eastern coastal Tanzania (Cyprinodontiformes Nothobranchiidae). 81089 records from Données de l'AFB acquises selon le protocole de pêche complète à un ou plusieurs passages. 7848 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 25 records from Sierraperla Jewett, 1954 (Plecoptera: Peltoperlidae), Distribution, Egg Morphology And Description Of A New Species. 2 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 2 records from Hangzhou-sediment-sample Raw sequence reads. 1 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 4 records from Two new species of Sweltsa (Plecoptera: Chloroperlidae) from China. 14 records from A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan. 16419 records from Vascular plants of south-central China. 144 records from BIRDRACE Punkbirder Helgoland. 277 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 3 records from Discovery of the first leaf litter inhabiting flea beetles in Brazil (Coleoptera: Chrysomelidae: Galerucinae) with description of two new genera and three new species. 4 records from A new species of the greeneye genus Chlorophthalmus (Teleostei: Chlorophthalmidae) from the central North Pacific. 2 records from Campydoroides manautei gen. et sp. nov. from New Caledonia and a reappraisal of the suborder Campydorina (Nematoda). 6 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 243 records from Fish species occurrences from selected near shore and riverine habitats in Lake Edward (2019). 264 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 22 records from Review of the Taiwanese Laccobius Erichson, 1837 (Coleoptera: Hydrophilidae) with description of a new species. 2 records from Cnemaspis rajakarunai sp. nov., a rock dwelling day-gecko (Sauria: Gekkonidae: Cnemaspis) from Salgala, an unprotected lowland rainforest in Sri Lanka. 61 records from Naturpark Kottenforst-Ville 15.6.09. 7 records from Lepidepecreoides stoddartae sp. nov. from the Falkland Islands (Amphipoda: Tryphosidae). 1654 records from The Belgica 121 expedition to the Western Antarctic Peninsula: a high resolution biodiversity census. 34 records from Happywhale - Killer Whale in Arctic Ocean. 2 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 173 records from FFH-Gebiet Klosterwasser/Burkau. 22 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 7 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 353 records from Données naturalistes de Hubert GUIMIER. 1523 records from Données naturalistes de Hervé BOUYON. 1112 records from Données de la collection Rousset -1947-2013. 2 records from Revision of the genus Systellapha Enderlein (Micropezidae, Taeniapterinae). 10 records from Ten new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Southeast Asia. 386 records from Thistle Heads and Ermerged Insects. 1 records from Aristolochia luudamcui (Aristolochiaceae), a new species from northern Vietnam. 1 records from A New Free-living Marine Nematode Species of the Genus Graphonema (Nematoda: Chromadorida: Chromadoridae) from Antarctica. 1 records from Acropoma profundum, a New Species of Lanternbelly (Teleostei: Perciformes: Acropomatidae) from the Solomon Islands. 69 records from PRESENCIA DE VISÓN AMERICANO EN TIERRA DEL FUEGO, MAGALLANES, CHILE. 34 records from Database of European river lamprey (Lampetra fluviatilis (Linnaeus, 1758)) actual samples deposited in the A.N. Severtsov Institute of Ecology and Evolution. 11 records from Notes on the Dianous aereus complex with description of a new species (Coleoptera, Staphylinidae). 301 records from Northern elephant seals post-breeding 2015 (aggregated per 1-degree cell). 17 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 430 records from Archaeal diversity of surface seawater (A3,A5,G3,G5) Targeted Locus (Loci). 176 records from Renaturierung Werse (Innenbereich Beckum). 23 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1a. 9536 records from FUEL - Herbário da Universidade Estadual de Londrina. 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 3 records from A new species of Flavoperla Chu, 1929 (Plecoptera: Perlidae) from Guangxi Zhuang Autonomous Region of southern China. 3564 records from Dragonfly (Odonata) species records up to 1997 held by Leicestershire Environmental Resources Centre. 2743 records from marine sediment metagenome Raw sequence reads. 4 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 1515 records from Dung Beetle Ecosystem Engineers. 130 records from Dubai Turtle Rehabilitation Project (aggregated per 1-degree cell). 16333 records from Seabirds in Norway - Estimated population sizes. 247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 16 records from Kenai National Wildlife Refuge, Alaska (KNWR) Fish observations (Arctos). 929 records from Photographs of higher plants, mosses, fungi, lichens, and algae. 1211 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 1338 records from Kallisti Limnes subsea pools Metagenome Study. 1991 records from Coleção de Ictiologia ABAM do Campus Sinop da UFMT. 2 records from Two new species of Spider Wasps (Hymenoptera, Pompilidae), Ctenagenia pagliano from Lebanon and Evagetes liane from Canary Islands. 445 records from South Lanarkshire peatland records 2013. 529 records from NEFSC Mid-Atlantic Marine Mammal Abundance Survey 2004. 8 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 83 records from Données du/de la naturaliste GAUTHIER Nicolas provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from First report of the old world genus Pelecystola in North America, with description of a new species (Lepidoptera, Tineidae). 468 records from Derbyshire Casual LEPIDOPTERA records - Casual records collated by Derby Museum.. 682 records from Transferts SI Faune - Données naturalistes opportunistes de Cedric DEVILLEGER. 1 records from A new, peculiar genus of Cossoninae (Coleoptera, Curculionidae) from Oman with description of a new species, larva and notes on biology. 639 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 4293 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 1 records from Diversity of methyl alkyl succinate synthase genes in hydrocarbon seep sediments (Raw sequence reads). 487 records from Field Museum of Natural History (Action) Mammals Sightings. 27 records from New distributional records of Staphylinina in Taiwan, including a new species of Miobdelus Sharp (Coleoptera: Staphylinidae: Staphylininae: Staphylinini). 13 records from Lane 6 Analysis. 3939 records from Census of plant species in Pahou forest reserve. 274 records from Agrarian stands of Irvingia gabonensis Aubry-Lecomte ex O'Rorke) Baill. in the department of Couffo in South Benin (West Africa). 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 6 records from Pauximyia, a new genus of Odiniidae (Diptera: Acalyptratae) with description of two new species from Brazil. 375 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 18 records from Lepidurus arcticus survey Northeast Greenland 2013. 153 records from VSN-Wiese. 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 2 records from A new species of Liriomyza Mik (Diptera, Agromyzidae) on okra in Brazil. 3107 records from Ibaraki Nature Museum, Fungi collection. 2 records from A new genus and species of anophthalmous Otiorhynchini from Greece, with a new synonymy and new combinations (Coleoptera: Curculionidae, Entiminae). 29 records from Fortalecimiento de la efectividad del manejo y la resiliencia de las áreas naturales protegidas para proteger la biodiversidad amenazada por el cambio climático. 4166 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 67 records from Relative abundance of ostracods in sediment core Sv09. 896 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 18 records from Révision du genre Danuriella Westwood, 1889 (Mantodea). 52008 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 49 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 8 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 7 records from A New Species Of Perlesta (Plecoptera: Perlidae) From North Carolina With Additional Records For North Carolina And Virginia. 296 records from HRC SCC Aerial-Based Monitoring Survey February 2010. 4142 records from Trondheim urban biodyversity survey. 40 records from Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 58 records from Swedish Malaise Trap Project (SMTP) - Banchini. 60 records from Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata). 186 records from (Table II) Abundance of epibenthic phyla and classes during RSS James Clark Ross cruise JR144. 303 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 13 records from New species of Hercostomus Loew, 1857 from Afrotropics (Diptera: Dolichopodidae) and key to Afrotropical fauna. 32635 records from R. L. McGregor Herbarium Lichen Collection. 660 records from Peces pelágicos de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 2 records from A revision of the spider genus Anemesia (Araneae, Cyrtaucheniidae). 11033 records from Oregon Bee Atlas Survey Data: 2018. 112 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 2872 records from UAM Fish Collection (Arctos). 5 records from University of Sargodha Herbarium. 8808 records from Survey of bumblebees in central Alberta - 2018. 70 records from Isotope tracer experiment: meiofauna counts. 20 records from Bird Specimens of The Cattle Museum. 557 records from Corn bunting breeding distribution in Scotland. 1210 records from NEFSC Marine Mammal Abundance Cruise 2004 Passive Acoustic Monitoring - Rainbow Click Detections. 845 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 336 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 4 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 2 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 153 records from Selztal bei Friesenheim. 19699 records from Banded Iron Formation and Greenstone survey data. 2 records from Foraging Greens and Hawksbill Bare Sand Island (aggregated per 1-degree cell). 1381 records from UCM Mammal Collection (Arctos). 41 records from Hydroptilidae (Trichoptera) of Angola, a new genus, seven new species, and five new records. 2 records from New records and checklist of Chilocorini (Coleoptera: Coccinellidae) from China. 65729 records from Natural History Museum, Vienna - Herbarium W. 1 records from The genus Mytilina in China, with description of a new species (Rotifera: Monogononta: Mytilinidae). 1 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 1 records from Salvia robertoana (Lamiaceae), a new species from Oaxaca, Mexico. 9 records from A new species of Proterhinus Sharp, 1878 (Coleoptera: Curculionoidea: Belidae) from Miti‘aro, Cook Islands, South Pacific. 2767 records from University of Colorado, Museum of Natural History Herbarium Bryophyte Collection. 1472 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Verdon_2017_12_18. 65 records from PELD - RLaC | Biologia reprodutiva e dieta de Amerotyphlops brongersmianus (Vanzolini, 1976) da Restinga de Jurubatiba, Rio de Janeiro, Brasil (Serpentes: Typhlopidae). 30 records from Feral Pigs - Sightings and Cull records - 2014-2015. 1 records from On the systematic status of Calliophis macclellandi nigriventer Wall, 1908 (Reptilia: Serpentes: Elapidae). 22 records from Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species. 1 records from Description of the larva of Orthemis ferruginea (Fabricius, 1775) (Odonata: Libellulidae). 1748 records from Floral visits on plants, InsectScale 2008. 66 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/574-1. 2 records from Description of four new species of Anelaphus Linsley (Coleoptera, Cerambycidae Cerambycinae, Elaphidiini), correction of the spelling of species-group names and description of the female of Anelaphus pilosus Chemsak and Noguera. 63 records from Cetacean coordinated transborder monitoring using ferries as platforms of observation off Tunisia 2013-2014 - Atutax. 2509 records from Kenya Wildlife Service, Laikipia Samburu Aerial Census, 2012. 3 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 53623 records from Arizona State University Vascular Plant Herbarium. 14 records from Two new genera and six new species of Stenosini (Coleoptera: Tenebrionidae Pimeliinae) from Myanmar (Burma), collected by René Fouquè. 413 records from Stoneworts in Wales. 85 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 3 records from Two new species of tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) with note on intraspecific variations. 576 records from Fungi Collection. 87 records from Données espèces - Expertise IPE 70. 555 records from Colección Entomológica Universidad Nacional de Colombia, Sede Palmira (CEUNP). 940 records from NOAA coral reef monitoring invertebrate data from sites across Micronesia from 2009-09-29 to 2015-09-25. 12 records from Two new genera and three new subterranean species of Hydrobiidae (Caenogastropoda: Truncatelloidea) from Tunisia. 3 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 3 records from A new species of snail-eating snakes of the genus Pareas Wagler, 1830 (Reptilia: Serpentes) from eastern Himalayas, India. 6 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 1148 records from ABC event data for Nyika Plateau, Buma Hills. 11 records from Three new species of the subgenus Jaynesia Allen, 1969 of the genus Tiphia Fabricius, 1775 (Hymenoptera: Tiphiidae: Tiphiinae) from China, with a key to all known species. 1 records from A new species of Pseudocrenilabrus (Perciformes: Cichlidae) from Lake Mweru in the Upper Congo River System. 29359 records from CAS Invertebrate Zoology (IZ). 14 records from Ophioderma hendleri sp. nov. (Echinodermata: Ophiuroidea: Ophiodermatidae) and its congeners from the Eastern Pacific. 41 records from Etude d'impact projet d’ouverture de carrière à Vaudoy-en-Brie. 5515 records from water Raw sequence reads. 55 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 3 records from See lilies of the genus Bathycrinus (Echinodermata, Crinoidea: Bathycrinidae) from the North-West Pacific hadal trenches. 6 records from Leafhopper tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) of the Indian subcontinent. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 65 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 119 records from Suivi des leucorrines sur le site du Marais du Plata. 25326 records from ALCB herbarium - Universidade Federal da Bahia - Herbário Virtual REFLORA. 2378 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Vascular Flora and Habitats: species of conservation concern (RELAPE) - [2010-2014]. 7 records from A review of Dinetus Panzer, 1806 with descriptions of five new species and keys to world species (Hymenoptera, Crabronidae). 83 records from Сypripedium guttatum Sw. in the Komi republic. 515 records from Kenai National Wildlife Refuge, Alaska (KNWR) Bird observations (Arctos). 626 records from NSW South Coast & ACT plants. 805 records from EDP Baixo Sabor: Birds - Construction and Reservoir Filling Phases - Vilariça Stream (MC1) [2013-2014]. 31 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 7 records from Descriptions Of The Adult Male And Female Genitalia Of The Genus Osobenus Ricker (Plecoptera: Perlodidae). 35 records from Ortsrand Zandershagen. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 2 records from Happywhale - Southern Right Whale Dolphin in South Atlantic Ocean. 62 records from artsprosjektet_48-13_monomyx. 1 records from Crickets of the genus Gryllus in the United States (Orthoptera: Gryllidae: Gryllinae). 505 records from National Frog Survey of Ireland 2010/2011. 405 records from Colección Ornitológica de la Universidad del Valle. 154 records from HRC USWEX Aerial-based Shoreline Surveys February and March 2011. 198 records from Chronicle of Nature - Phenology of Insects of State Nature Reserve Kivach. 794 records from USWTR JAX Aerial Survey -Right side- 2009-2010. 293 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Privolzhskaya Lesostep. 1 records from On the Italian species of Drusilla L, 1819, with a note on D. taygetana A (Coleoptera: Staphylinidae, Aleocharinae). 10 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 7 records from Revision of the South American species of Austrothaumalea Tonnoir (Diptera Thaumaleidae). 1 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 797 records from The ‘ red-tailed’ Lasioglossum (Dialictus) (Hymenoptera: Halictidae) of the western Nearctic. 5246 records from The Fungal Literature-based Occurrence Database for the Southern West Siberia (Russia ). 188 records from Données de Mammifères marins. Mission Sanctuaire AGOA de 2012 à 2014. 576 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 161 records from Ten new species of Phyllodoce Lamarck, 1818 (Phyllodocidae, Annelida) from Brazil. 14 records from The Goblin spider genus Xestaspis in Sri Lanka (Araneae: Oonopidae). 299 records from Chronicle of Nature - Phenology of Birds of Central Forest State Nature Biosphere Reserve. 48 records from Bald Head Island 2004: Loggerhead Turtles (aggregated per 1-degree cell). 5 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 3 records from Indian Hecalina (Hemiptera: Cicadellidae: Deltocephalinae: Hecalini) with description of three new species. 41676 records from Tagged Seal Location Data from SOGLOBEC. 333 records from Données naturalistes de Renaud PUISSAUVE. 64253 records from Dry Tortugas Reef Visual Census 2010. 237 records from Suivi ornithologique par IPA et IKA réalisés dans la Réserve nationale de l’Étang de Saint-Paul en 2012 et 2014. 376 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 8 records from Contribution to the Asian and Afrotropical species of the genus Dyschiriodes (Coleoptera: Carabidae: Scaritinae). 1 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 6 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 5 records from A new pelvic-less species of Melanorivulus Costa (Cyprinodontiformes: Cynolebiidae), with a discussion on the pelvic-fin absence in killifishes. 107 records from Three new species of Oxypoda from Spain, Armenia, and Ukraine with notes on the fauna of Armenia (Coleoptera: Staphylinidae: Aleocharinae). 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 1 records from The Calliphoridae (Diptera) of Armenia. 651 records from Réseaux écologiques/Trame verte et bleue. 1 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 1 records from Happywhale - Harp Seal in North Pacific Ocean. 3 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 8006 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 6 records from Review of Scatimus Erichson (Coleoptera: Scarabaeidae) in Colombia with the description of a new species. 120797 records from Wild bees of Belgium. 3 records from Review of the genus Pseudolathra Casey, 1905 (Coleoptera: Staphylinidae: Paederinae) of Réunion Island. 22 records from Observations de tortues marines dans l'archipel de Saint-Pierre et Miquelon. 54 records from Données du/de la naturaliste Villalta Rémi provenant de la base de donnée du SINP Île-de-France CETTIA. 5 records from New species of the plesiomorphic genus Nixonia Masner (Hymenoptera, Platygastroidea, Platygastridae) from South Africa. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 756 records from Mokihinui and Karamaea small tributaries and seeps. 245 records from Aspilanta new genus (Heliozelidae) specimen data. 558 records from If_Ecologie_Conseil_2017_12_18. 228 records from Some zoological observations in Kherson region of Ukraine. 654 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hemiptera (ZUFMS-HEM). 264 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (rescate). 900 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Plantas Tapachula). 140 records from Taxonomic revision of West African cone snails (Gastropoda: Conidae) based upon mitogenomic studies: implications for conservation. 421 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 1355 records from Antarctic Lakes Brine Raw sequence reads. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 5 records from A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae). 2110 records from Mid-Pleistocene (800-400 ka) planktic foraminfer assemblages of IODP Site 306-U1314. 5938 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 66 records from Loggerheads in the Tyrrhenian Sea (aggregated per 1-degree cell). 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 57 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 8367 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 2952 records from Colección Entomológica CDMB. 3 records from NZCS Invertebrates New Collection After 1987. 1 records from Happywhale - Ringed Seal in North Atlantic Ocean. 757 records from Lepidoptera (Specimens NRM). 214 records from Colección nacional de palmas de Colombia - JBQ. 15327 records from Biodiversidad asociada al gasoducto Paiva-Caracolí. 54 records from ROC RSPB Farmland Species Survey Dataset. 19 records from The cicadas (Hemiptera: Cicadidae) of Ecuador including the description of five new species, a new subtribe, four new synonymies, and fifteen new records. 205 records from Wild boar sightings held by Andy Riches. 198 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 6054 records from Community Foundation for Ireland Records. 38 records from Bald Head Island 2007: Loggerhead Turtles (aggregated per 1-degree cell). 489 records from Caracterización bionómica de zonas de dragado y de afección de obras en la Ría de Ferrol. 68 records from First records and two new species of sipunculans (Sipuncula) from the Southern Mexican Pacific. 4317 records from Collection of saproxylic and xylobiont Beetles. 2526 records from sea water Picoeukaryotic Community Raw sequence reads Raw sequence reads. 71 records from IOW Natural History & Archaeological Society Marine Records. 13 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 6189 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 71 records from Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010. 2097 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 10389 records from Seawater metagenome Targeted loci environmental. 342 records from Phytoplankton abundance measured on water bottle samples at station PS65/545-1. 135 records from Waldi-Weiher. 470 records from Gewann Krampf (Heilbronn). 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 21 records from Données de NICOLAS Vincent (SAPROX). 607 records from Inventory of Bassila forest (North-Benin). 6440 records from Microbial ecology of bacteiral community in sediment from adjacent waters of Rushan Bay. 2 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 2572 records from seawater metagenome Metagenome. 1917 records from Diet results from Adelie penguins at Bechervaise Island and Whitney Point, 2012/13. 3019 records from Heliconiine Butterfly Collection Records from University of Cambridge. 6 records from Hemichordata collection of National Museum of Nature and Science. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 1468 records from Colección Regional de Equinodermos de la Peninsula de Yucatan. 4 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 4 records from Determinación de la clase Reptilia presente en el corregimiento de Juanchaco, Valle del Cauca, Colombia para el mes de Septiembre de 2017. 355 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 508 records from Northern elephant seals post-molting 2017 (aggregated per 1-degree cell). 255 records from Tejidos colectados en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 79 records from Birdrace-Bielefinken-Bielefeld. 8549 records from Kenai National Wildlife Refuge, Alaska (KNWR) Insect specimens (Arctos). 107 records from Müritz-Nationalpark. 70 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 5774 records from Colección Limnológica Universidad de Antioquia. 378 records from Rock ptarmigan (Lagopus muta) radio telemetry in Lierne, Norway. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 503 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 272 records from Wald am Schloss Wittgenstein Bad Laasphe. 13900 records from Tachinid Recording Scheme - Tachinid fly records verified via iRecord. 239 records from Shoreline fish distribution in Italian lakes assessed by electrofishing. 21160 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 2 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 23 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 5445 records from Conservación y monitoreo de anfibios en riesgo de extinción en Chiapas. 1309 records from Données naturalistes de LUPOLI Roland. 68 records from Données du/de la naturaliste JOSSERAND oriane provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from A new species of Aframomum (Zingiberaceae) from Central Africa. 40 records from Phytoplankton abundance at station Sechin_2003-10-03_2, Casma, Peru. 574 records from Catopsilia butterfly specimens at Museum Zoologi Bogor, Indonesia. 816 records from Inventarios de la biodiversidad en el piedemonte subandino de Yopal. 96 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 2 records from Two new species of stargazers of the genus Uranoscopus (Teleostei: Uranoscopidae) from the western Pacific Ocean. 2 records from First record of the myrmicine ant genus Syllophopsis Santschi, 1915 (Hymenoptera Formicidae) from India with description of a new species. 16 records from NC Aquariums Cold Stunned Sea Turtle Monitoring (aggregated per 1-degree cell). 355 records from Données naturalistes de François BRETON. 7 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 1157 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2004. 5 records from Copepoda (Siphonostomatoida: Dirivultidae) from Hydrothermal Vent Fields on the Central Indian Ridge, Indian Ocean. 2743 records from EDP Foz Tua: Terrestrial Birds, Winter (point counts) - Ecological Monitoring Program [2011-2017]. 67 records from Post-nesting migration of loggerhead turtles around Japan 2005 (aggregated per 1-degree cell). 559 records from Leicestershire and Rutland Reptile Records to 2011. 5640 records from Solenosmilia matrix annotations and VME habitat identification in video from voyage IN2018_V06, Australia (2018). 48 records from Collection Vermes - ZMB. 2 records from Culture Collection of Algae. 130 records from BIRDRACE - The famous Grouse feat. The James. 7 records from Parasitoides de Cochinilla. 1 records from Mumetopia interfeles sp. nov., a new species of Anthomyzidae (Diptera) occurring en masse in an urban grassy habitat in Chile: its taxonomy, phylogeny and biology. 6909 records from VIES herbarium - Universidade Federal do Espírito Santo - Herbário Virtual REFLORA. 2 records from Baetis pentaphyllus sp. nov., a new species of mayfly (Ephemeroptera: Baetidae) from the Russian Far East. 294 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 372 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 1 records from Taxonomic review of the genus Compsiluroides Mesnil (Diptera: Tachinidae), with the description of a new species. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 5 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 74 records from Anfibiofauna asociada a la quebrada Giginia, corregimiento de Doña Josefa, Municipio del Atrato - Chocó, 2019. 37 records from FBIP: scallop population genetics. 18 records from Schulgarten der Gesamtschule Am Heidberg. 1886 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 22 records from Two new Hottentotta species from Iran, with a review of Hottentotta saulcyi (Scorpiones: Buthidae). 12 records from New species of Condylostylus Bigot (Diptera: Dolichopodidae) from Comoros Madagascar, Tanzania and South Africa, with key to Afrotropical species. 1270 records from Données du/de la naturaliste Lantz André provenant de la base de donnée du SINP Île-de-France CETTIA. 378 records from (Table 1) Distribution of planktonic foraminifera from samples spanning the Cretaceous-Tertiary boundary at ODP Hole 207-1259C. 2 records from The genus Synergus Hartig (Hymenoptera: Cynipidae: Synergini) in the New World: a complete taxonomic revision with a key to species. 34 records from Read between the lineata: A revision of the tattooed wasps, Zagrammosoma Ashmead (Hymenoptera: Eulophidae), with descriptions of eleven new species. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 3 records from Society Islands beach bum black flies (Diptera: Simuliidae). 445 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 62 records from Données naturalistes de BONCHE Jérôme. 304 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 4 records from Happywhale - Spinner Dolphin in North Atlantic Ocean. 3501 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 9 records from Character state variation within Dendrothrips (Thysanoptera: Thripidae) with a revision of the species from China. 5 records from Biodiversity of spider mites (Acari: Tetranychidae) in Serbia: a review, new records and key to all known species. 4321 records from Hormigas del Museo de Entomología de la Universidad del Valle. 11 records from Reptiles Specimens of Akita Prefectural Museum. 147 records from UWIZM Snakes. 10531 records from Actualización del conocimiento de la diversidad de especies de invertebrados marinos bentónicos de aguas someras (<50m) del Sur del Golfo de México. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 182 records from Tejidos colectados en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 141 records from Biodiversity survey of Rugezi wetland, Year 2013. 449 records from Artsprosjekt Pyrenomycetes. 4 records from Crustáceos del municipio Santa Bárbara, Santander - Proyecto Santander BIO. 6654 records from NOAA coral reef monitoring benthic data from sites across Micronesia from 2009-09-29 to 2015-09-25. 121 records from Etude écologique du Parc des Lilas (94). 2 records from Nouveautés dans le genre Lomariopsis Fée (Pteridophyta, Lomariopsidaceae) à Madagascar: trois espèces nouvelles et une espèce africaine nouvellement signalée. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 1 records from A new species of Leiochrides Augener, 1914 (Annelida: Capitellidae) from the Beibu Gulf, South China Sea. 2 records from Leptagrion itabaiana sp. nov. (Odonata: Coenagrionidae) from Serra de Itabaiana National Park, Sergipe state, Northeastern Brazil. 2 records from Yunnan-Guizhou Plateau: a mycological hotspot. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 6 records from A New Species Of Perlesta (Plecoptera: Perlidae) From New York. 21 records from Cape Verde (Cabo Verde) 2005: Loggerhead Turtles (aggregated per 1-degree cell). 6 records from Benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2010. 60 records from Fish species observations from a monitoring survey of two Lake Victoria affluent rivers (Rivers Kagera and Sio). 82 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 36 records from BIOMEO_2017_12_18. 138 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 10 records from Contribution to the knowledge of Carabidae in Iran with the descriptions of five new taxa, proposing of four synonyms and providing of nine new records (Insecta: Coleoptera). 1 records from A taxonomic note of Pterocephalus (Caprifoliaceae) from N Iran. 2 records from Mammals in the collection of Zoological Museum of NSNHM (the National Science and Natural History Museum at the National Academy of Sciences of Ukraine, Kyiv): Erinaceidae, Talpidae, Soricidae, Myoxidae, Sminthidae. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 1 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 42 records from Bosque Mesófilo de Montaña de México. 52 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 3917 records from Empire Wind Digital Aerial Wildlife Surveys for BOEM Lease Area OCS-A 0520, Equinor Wind US LLC, February - December 2019. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 14184 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 5 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 24 records from Happywhale - Crabeater Seal in Southern Ocean. 10 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 1509 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 4 records from Mammal specimens of Komatsu City Museum. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 12 records from Urban Barcode Project - Fungi. 6057 records from 2018_nsmk_biodiversity_pi. 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 261 records from ACT and Southern Tablelands Weed Spotter. 4 records from Taxonomic review of the ant genus Dilobocondyla from China (Hymenoptera: Formicidae), with a revised key to the known species. 41 records from Örtzemündung (Stedden). 51063 records from National Stag Beetle Surveys (Great Stag Hunts). 1190 records from Tracking data from a free-roaming female cheetah released into the Pilanesberg National Park, South Africa. 86616 records from Marine Offshore Seabed Survey data held by JNCC. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 1 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 316 records from Données naturalistes de Monsieur LEFEBVRE François. 14 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 1230 records from Données du naturaliste Marquet Jacques provenant de la base de donnée du SINP Île-de-France CETTIA. 6579 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Entomologica). 12 records from Mamíferos del municipio de Santa Bárbara, Santander - Proyecto Santander BIO. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 61931 records from Herbarium of Taiwan Forestry Research Institute. 3 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 3 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 2 records from New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa. 23 records from Ackerrain Plönhagen. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 783 records from Données odonates. 56 records from Malawi-Histeridae-Biodiversity-Data. 3 records from Swiss National Diplopoda Databank. 2026 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 10 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 18 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 1 records from A new species of the genus Aalatettix Zheng & Mao (Orthoptera, Tetrigoidea Tetrigidae) from China. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 1 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 313 records from BIRDRACE Gätkes Erben. 1 records from New species of Chaetonerius Hendel (Diptera: Neriidae) from the Oriental Region. 12 records from The genus Semicerura (Collembola; Isotomidae) in Asia. 20747 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 28 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 23 records from Happywhale - Short-finned Pilot Whale in North Atlantic Ocean. 159 records from EDP Foz Tua Otter (Lutra lutra) [transects] - Ecological Monitoring Program (2011-17). 11 records from A new species of the genus Tetragonopterus Cuvier, 1816 (Ostariophysi: Characiformes: Characidae) from the rio Tocantins drainage, Brazil. 518 records from Carabidae of the European North-East of Russia. 5 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1040 records from Données de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS 2015 Chiroptères, Maculinea, Cistude d'Europe. 2225 records from Données naturalistes d'Anaïs MAS. 862 records from Palynological analysis of sediment core GeoB9508-5. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 4 records from Novel taxa of Cheilostomata Bryozoa discovered in the historical backlogs of the Iziko South African Museum. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 65 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 15 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 30 records from HRC CRC Small Vessel-Based Monitoring Surveys December 2010. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 3472 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 5462 records from Arachnids (Aranei, Opiliones) from grass stand and forest litter in the Urals, Russia. 1168358 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 33 records from Capobula gen. nov., a new Afrotropical dark sac spider genus related to Orthobula Simon, 1897 (Araneae: Trachelidae). 14 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 3 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 69 records from Bishop's University Insect Collection (BUIC). 18 records from ALTERECO_2017_12_18. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 24 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 5346 records from Sediment metagenome. 511958 records from BioFokus. 15253 records from Anymals+plants - Citizen Science Data. 55 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 1563 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 1 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 16705 records from Sierra Nevada Atmospheric-Pollen Data set (SNOWPOLL). 991 records from Données du/de la naturaliste CARON Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 26 records from Happywhale - Blue Whale in Southern Ocean. 7722 records from Happywhale - Humpback Whale in North Atlantic Ocean. 105427 records from ABV - Common breeding birds in Flanders, Belgium (post 2016). 5156 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 1779 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 167 records from CNAN/Scorpiones. 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 5 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 6 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 3093 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 424 records from Collection de C.C.H. Jongkind aux Monts Nimba. 2 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 2 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 69 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 12094 records from Amino acid addition experiment Metagenome. 3131 records from Données DREAL Centre-Val de Loire - Faune - 2018. 55 records from Vegetationsmatrix schorfheide alb 2008 durchgang2. 54632 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 1288 records from Comparative metagenome analysis of normal and arsenic contaminated soils from ballia district, Uttar Pradesh, India. 9054 records from Highland bird data 2002 - 2003 - non-breeding records. 7712 records from 1994-2020 Capercaillie Cold Searches Data, Scotland. 7 records from Revision of the genus Cobbionema Filipjev, 1922 (Nematoda, Chromadorida, Selachinematidae). 9002 records from Uncultured Environmental Isolate Targeted loci environmental. 3418 records from RNF - Données du Parc Naturel Régional du Vercors. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 206 records from Registros de geckos en Colombia asociado al proyecto: The small world of Lepidoblepharis. 100 records from Family Geraniaceae in CSBG SB RAS herbarium collections (NS, NSK). 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 1931 records from The hoverfly collection (Diptera, Syrphidae) of the International Institute of Tropical Agriculture (IITA) at Calavi (Benin). 4 records from A new South American species of Banasa Stål (Hemiptera: Heteroptera: Pentatomidae: Pentatominae): from egg to adult. 10 records from The InBIO Barcoding Initiative Database: A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann, 1870 (Lepidoptera, Depressariidae). 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 912 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 1 records from Happywhale - North Atlantic Right Whale in North Atlantic Ocean. 16786 records from NE AVH data. 2172 records from ConDidact Citizen Science Surveys - Snails 2006. 98 records from Description of lithologic section units of IODP Hole 325-M0033A. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 21 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 1845 records from Biodiversidad selecta de los humedales de Laguna de Términos - Pantanos de Centla (Plantas). 47 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 1139 records from SWECO. 4227 records from Données naturalistes de Loïc SALAUN. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 237 records from Virginia CZM Wind Energy Area Survey- Left side - January 2014 through March 2016. 2172 records from EDP Foz Tua: Terrestrial Birds (transects) - Ecological Monitoring Program [2009-2012]. 13338 records from EAC - Herbário Prisco Bezerra. 2295 records from East Ayrshire Species Database. 100 records from Euroants. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1496 records from Leif Richardson Vermont Bee Specimens. 3 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from PRA Sonneur à ventre jaune - étude de répartition. 1971 records from Collection Crustacea - ZMB. 471 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 4 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 1 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 173 records from Georgia Aquarium/DomSeTCO Leatherback's of Dominica (aggregated per 1-degree cell). 9 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 266 records from Structure of waterbird assemblages in fragmented coastal wetlands of Northeastern Algeria. 1 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 1 records from Le genre Oxyanthus DC. (Rubiaceae) en Afrique de l’Ouest: description d’une nouvelle espèce. 4 records from Polycentropus dinkinsorum (Trichoptera: Polycentropodidae), a newly described caddisfly species from the southern Appalachian Mountains, USA. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 87 records from Microzooplankton abundance measured on water bottle samples at station PS65/514-2. 23 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 10 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 1 records from New collections of freshwater crabs from northern Madagascar, with the description of a new species of Foza Reed & Cumberlidge, 2006 (Brachyura, Potamonautidae), and comments on their conservation status. 4 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 19 records from Description of lithologic section units of IODP Hole 325-M0035A. 4 records from Four new species of Rhyacophila Pictet 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia. 1 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 22 records from Five new and five known species of the genus Tylencholaimus de Man, 1876 (Nematoda: Dorylaimida: Tylencholaimoidea) from Western Ghats of India. 321 records from Canary Islands - OAG (aggregated per 1-degree cell). 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 13 records from Warnowufer Groß Klein. 4082 records from Meetnetten.be - Population counts for dragonflies in Flanders, Belgium. 45 records from Tejidos de los ejemplares colectados en la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 2 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 1750 records from Colección del Herbario de la Universidad de los Llanos. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 1291 records from Leicestershire and Rutland Mature trees Inventory 2011. 10 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C. 9 records from Valentin Moser Bats. 2 records from A new species of Glyphocrangon (Crustacea, Decapoda, Caridea, Glyphocrangonidae) from the Austral Islands, French Polynesia. 92 records from Planktonic bacterial communities in the arctic Canada Basin and Kongsfjorden. 10 records from Two new endangered species of Polygala series Trichospermae (Polygalaceae), endemic to the Cerrado domain, Tocantins State, Brazil. 4 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 2 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 7 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 49 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile. 33560 records from Extracellular DNA marine sediment Targeted Locus (Loci). 279 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 384 records from "Schwarzwassertal" bei Pobershau. 2041 records from marine metagenome Targeted Locus (Loci). 331 records from Plan de vertebrados de la Patagonia. 1170 records from Springtales from lichen communities at Kollåsen in Norway. 21 records from Murciélagos de la isla de Providencia. Expedición Seaflower 2019 proyecto Colombia BIO. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 1 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 303651 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 71 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 975 records from Danielsberg (Mölltal, Kärnten). 95 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 12960 records from LPO_PACA_2017_12_18. 81 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 2 records from A new species of genus Prosopigastra A. Costa (Hymenoptera: Crabronidae: Crabroninae) from China, with a key to the Chinese species. 8 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 661 records from Targeting a portion of central European spider diversity for permanent preservation. 194 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 7485 records from Census of species recorded during phytosociological surveys in Benin. 6977 records from 2019_NSMK_PL_2. 702 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 92 records from Sonidos de la Ecoreserva La Tribuna (Neiva, Huila) - Proyecto FIBRAS. 2761 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 1 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 1 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 2412 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1334 records from Collection Pisces SMF. 781 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 37088 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 58 records from MEXU/Tipos de plantas vasculares. 2 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 12202 records from Pelagic Gulf of Mexico Targeted loci environmental. 12 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 1 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 242 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 1270 records from University of Valencia cetacean surveys in the Spanish Mediterranean 2000-2003. 201 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (4), 2011 - Données faune. 10 records from Bachpatenschaft Beeke. 462 records from Données du/de la naturaliste Dodelin Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 2568 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 341 records from SPC CoFish Invertebrates Observations Niue 2005. 12 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 1 records from First Record of Holothuria (Cystipus) dura (Echinodermata: Holothuroidea) from Japan, with Notes on Locomotion. 167 records from Artenvielfalt auf den Elbwiesen (Dessau). 1009 records from Données naturalistes de Daniel PAVON. 356 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 15 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (ANONAU). 306 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 248 records from A revision of the minor species group in the millipede genus Nannaria Chamberlin, 1918 (Diplopoda, Polydesmida, Xystodesmidae). 60 records from Caracterización de la fauna reptiliana asociada a la cuenca del río Atrato, para el estudio de su navegabilidad, Quibdó - Chocó, 2012. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 260846 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 9 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibdó - Chocó, 2019. 4 records from Leuctra Pinhoti, A New Species Of Stonefly (Plecoptera: Leuctridae) From Alabama, U. S. A.. 7 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 2 records from Bryoerythrophyllum subcaespitosum (Pottiaceae), a new combination for a neglected species from South America. 12 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 4 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 270 records from BIRDRACE Niederlausitz-Team. 2 records from Revisions to the faunas of Andrena of the Iberian Peninsula and Morocco with the descriptions of four new species (Hymenoptera: Andrenidae). 319 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 10 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 20 records from Happywhale - Sei Whale in South Pacific Ocean. 13 records from New and noteworthy species of Begonia (Begoniaceae) from Vietnam and Laos. 400 records from Mushrooms Flora of Nepal at National Herbarium and Plant Laboratories (KATH). 37 records from Two new species of Tipula (Vestiplex) Bezzi (Diptera, Tipulidae) from Northwest China. 114 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 1 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 2 records from Descriptions of two new shell-dwelling species of Metriaclima (Cichlidae) from Lake Malaŵi, Africa. 101 records from TRAS LA RUTA DE LAS TORTUGAS GOLFINAS EN LOS CABOS, BCS 2009-2018 !! (aggregated per 1-degree cell). 375 records from CG04_2017_12_18. 718 records from Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera Cicadellidae: Eurymelinae). 3 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 22 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 517 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 6612 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 228 records from FBIP: Identification of polychaetes used as bait. 84820 records from Denver Museum of Nature & Science - Entomology. 3 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 42 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 10707 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 16359 records from Database for alien invasive plants occurrences in Germany. 5 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 33 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 466 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 960 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 8313 records from 成龍溼地鳥類生態紀錄. 2 records from Chalinochromis cyanophleps, a new species of cichlid fish (Teleostei: Cichlidae) from Lake Tanganyika. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 74 records from UNCW JAX Aerial Survey -Left side- 2017. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 237709 records from Abundance of Rocky Reef Fishes, Invertebrates and Algae, Reef Check California (RCCA), 2006 - 2017. 1928 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 4193 records from OUPR - Herbário "Professor José Badini". 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 27339 records from National Biodiversity Data Bank. Observation records, 1900-2014. 100 records from Registros de Palma de cera palma (Ceroxylon quindiuense) por medio de fotografías aéreas en el parque Chingaza. 170 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 946 records from Occurrence database of bryophytes and native animals of southern Chile. 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 9066 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 1 records from Two new species of Corynellus Bates, 1885 (Coleoptera: Cerambycidae: Cerambycinae). 1 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 5 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 92 records from Nottekanal, Klasse 7 - 10. 12 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 30 records from Amoeboid protists isolated from ancient Siberian permafrost. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 9 records from Swedish Malaise Trap Project (SMTP) - Bethylidae. 13700 records from données aranéologiques de CORNIC Jean-François. 86 records from Suivi de la flore patrimoniale de la RNR de Saint-Assise (77) dans le cadre d'un stage de M2. 48 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 74 records from Données espèces - Expertise IPE 69. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 286 records from Riqueza y distribución de briófitos reófilos en el predio Golconda, ubicado en el municipio de Hato, Santander. 401 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 2 records from A taxonomic revision of the Palaearctic members of the Formica rufa group (Hymenoptera: Formicidae) - the famous mound-building red wood ants. 1193 records from NEFSC North Atlantic Marine Mammal and Turtle Aerial Abundance Survey 2007. 5353 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 1 records from Filogeografia mitocondrial y nuclear de la Tangara rosada Rhodinocichla rosea (Lesson, 1832): el efecto del aislamiento geográfico y el nicho ecológico en los procesos de divergencia evolutiva.. 50 records from Flora und Fauna im Brexbachtal. 652 records from Insectos asociados a cultivos de Albahaca y Ají en Santa Marta. 2 records from Distributional and taxonomic notes on the crab spider genus Talaus Simon, 1886 with description of a new species (Araneae: Thomisidae). 810687 records from MICROBIS database. 565 records from Fauna marina de la costa vasca - Sistema de Información de la Naturaleza de Euskadi. 190 records from Herpetofauna laguna El Tinije. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 123 records from Birdrace-Professorenteam-Münster. 6926 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 3 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 426 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 377714 records from Swiss National Grasshoppers Databank. 391 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 78002 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 30091 records from BIOWIDE eDNA Fungi dataset. 21025 records from Weevil and Bark Beetle records via iRecord. 320 records from Caracterización hidrogeológica para el diagnóstico ambiental de alternativas del proyecto hidroeléctrico San Bartolomé (ISAGEN y HMV).. 6 records from Chronicle
Keywords: GBIF; biodiversity; species occurrences